Inorganic coating film and coating liquid

The inorganic coating film with dispersed nanobubbles in a glass-based composition addresses the challenge of high cost and weight in coating applications by reducing material usage while maintaining performance and protection, specifically for articles like automobiles.

JP2024174834APending Publication Date: 2024-12-17HARDOLASS HLDG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024087590
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-05
Filing Date
2024-05-30
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Coating liquids containing organic polysilazane are expensive, and reducing their application amount while maintaining a predetermined film thickness is necessary to avoid increasing the weight and cost of coated articles, particularly in applications like automobiles, which can affect fuel efficiency and performance.

Method used

An inorganic coating film composed of glass with dispersed nanobubbles and a coating liquid containing polysilazane, siloxane, and an inert organic solvent, which reduces the amount of coating material needed by incorporating fine spherical spaces, thereby minimizing weight and cost without compromising on impact resistance and corrosion resistance.

Benefits of technology

The inorganic coating film achieves reduced coating material usage, lowering the weight and cost per unit area while maintaining excellent impact resistance and corrosion resistance, preventing cracks and peeling, and ensuring long-term protection of the coated surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174834000001_ABST
    Figure 2024174834000001_ABST
Patent Text Reader

Abstract

To provide an inorganic coating film capable of reducing a coating amount to an article being a coating object, usable inexpensively, and capable of minimizing an increase of a weight of an article including the inorganic coating film when coated onto a surface of the article being a coating object.SOLUTION: An inorganic coating film 13 includes glass as a main component in a cured state and is configured to coat a surface 12 of an article 11 being a coating object. Inside the inorganic coating film 13, nanobubbles with an average particle diameter D90 of less than 1 μm are dispersed and mixed (dispersed and dissolved) in a prescribed density. In the inorganic coating film 13, an average particle diameter D90 of the nanobubbles is less than 1 μm, and preferably, an average particle diameter D50 is within a range of 1 nm to less than 500 nm. In the inorganic coating film 13, a content rate of the nanobubbles is within a range of 10 to 95 vol.%. A total number of nanobubbles per 1 mm2 of the inorganic coating film 13 is within a range of 107 to 1012 bubbles / 1 mm2.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an inorganic coating film for coating the surface of an article to be coated, and a coating liquid for forming the inorganic coating film. [Background technology]

[0002] A coating liquid is disclosed that contains 20-60wt% of organic polysilazane, 5-15wt% of alkyl silicate condensate, and 0-80wt% of organic solvent, and the content of methyl groups in the organic polysilazane is 50% or more (see Patent Document 1). In this coating liquid, the organic polysilazane reacts with moisture to form a coating layer of an inorganic-organic composite structure in which an organic functional group is bonded as a side chain to a part of the main chain by siloxane bond, and the alkyl silicate condensate acts as a crosslinking agent to form a crosslinked structure in the coating layer, thereby reducing the elastic modulus of the coating film and maintaining flexibility even if the film thickness is more than a certain level. Therefore, the coating film can follow the deformation of the article to be coated, the occurrence of cracks and peeling is prevented, and impact resistance and corrosion resistance can be ensured. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2021-14514 A Summary of the Invention [Problem to be solved by the invention]

[0004] Since the coating liquid containing organic polysilazane is expensive, it is desired to reduce the coating amount (coating amount) of the coating liquid on the surface (front and back) of the article to be coated and use the coating liquid inexpensively. However, since the coating film exerts its effect by coating the surface of the article to be coated with a predetermined film thickness, it is necessary to ensure a predetermined film thickness for the coating film after the coated coating liquid is hardened, and the coating amount cannot be reduced unconditionally. In addition, when the specific surface area of ​​the article to be coated with the coating liquid is large and the coating liquid is coated on the entire article, the weight of the article including the coating film increases even though the film thickness of the coating film formed by hardening the coating liquid is small. For example, when the article to be coated with the coating liquid is an automobile, the weight of the automobile including the coating film increases, and the fuel efficiency and acceleration performance may decrease.

[0005] An object of the present invention is to provide an inorganic coating film that can reduce the amount of coating on an article to be coated and can coat the surface of the article at low cost. Another object of the present invention is to provide an inorganic coating film that can minimize the increase in weight of an article including an inorganic coating film when the surface of the article to be coated is coated. Another object of the present invention is to provide a coating liquid that can reduce the amount of coating on an article to be coated and can be used at low cost. Another object of the present invention is to provide a coating liquid that can minimize the increase in weight of an article including an inorganic coating film when the surface of the article to be coated is coated. [Means for solving the problem]

[0006] The first premise of the present invention for solving the above problems is an inorganic coating film that, in a hardened state, contains glass as a main component and covers the surface of an article to be coated.

[0007] A first feature of the present invention in the first premise is that a large number of minute, independent spherical spaces are dispersed and mixed inside the inorganic coating film.

[0008] As an example of the present invention having the first characteristic, the spherical space is formed by nanobubbles, and the average diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90 The nanobubbles are dispersed and mixed at a predetermined concentration inside the inorganic coating film.

[0009] As another example of the present invention having the first characteristic, the average particle diameter D of nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 The nanobubbles are dispersed and mixed at a predetermined concentration inside the inorganic coating film.

[0010] In another example of the present invention having the first characteristic, the content of nanobubbles in the inorganic coating film is in the range of 10 to 95 vol. %.

[0011] In another example of the present invention having the first characteristic, the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them.

[0012] A second premise of the present invention for solving the above problems is a coating liquid which, in a hardened state, forms an inorganic coating film containing glass as a main component on the surface of an article to be coated.

[0013] The second feature of the present invention in the second premise is that the coating liquid is made by mixing a liquid silicon material consisting of at least one of polysilazane and siloxane, an alkyl silicate condensate, and an inert organic solvent in a predetermined mixing ratio, and a large number of independent fine spherical spaces are dispersed and mixed inside the coating liquid.

[0014] As an example of the present invention having the second characteristic, the spherical space is formed by nanobubbles, and the average particle diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90 The nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration.

[0015] As another example of the present invention having the first characteristic, nanobubbles are dispersed and mixed in the coating liquid in a negatively charged state, and the average particle diameter D 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 The nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration.

[0016] In another example of the present invention having the first characteristic, the content of nanobubbles in the coating liquid is in the range of 10 to 95 vol. %.

[0017] In another example of the present invention having the first characteristic, the blending ratio of the silicon material to the total mass of the coating liquid before nanobubbles are mixed in is in the range of 30 to 60 wt%, the blending ratio of the alkyl silicate condensate to the total mass of the coating liquid before nanobubbles are mixed in is in the range of 10 to 15 wt%, the blending ratio of the inert organic solvent to the total mass of the coating liquid before nanobubbles are mixed in is in the range of 30 to 60 wt%, the viscosity of the coating liquid at 20°C into which the nanobubbles are dispersed is in the range of 0.98 to 1.008 mPa s, and the rising speed of the nanobubbles in the coating liquid at 20°C into which the nanobubbles are dispersed is in the range of 0·000015 to 0.00005 mm / min.

[0018] In another example of the present invention having the first characteristic, the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these. Effect of the Invention

[0019] According to the inorganic coating film of the present invention, a large number of independent fine spherical spaces are dispersed (dispersed and dissolved) inside the inorganic coating film, so that the ratio of the inorganic coating film itself per unit area of ​​the inorganic coating film can be reduced by the large number of fine spherical spaces, and the amount of the inorganic coating film itself is reduced when the surface (front and back) of the article to be coated is coated, so that the amount of the inorganic coating film coated on the article can be reduced, and the unit price of the coating film per unit area of ​​the surface of the article can be reduced by the reduction in the amount of coverage compared to when the inorganic coating film does not have spherical spaces dispersed therein, so that the surface of the article can be coated inexpensively with the inorganic coating film. Compared to when the inorganic coating film does not have spherical spaces dispersed (dispersed and dissolved) therein, the inorganic coating film has a reduced mass per unit area, so that when the inorganic coating film covers the surface of the article to be coated, the increase in the weight of the article including the inorganic coating film can be minimized. For example, when the article coated with the inorganic coating film is an automobile, the increase in the weight of the automobile including the inorganic coating film can be minimized, and the decrease in fuel efficiency and acceleration performance of the automobile can be prevented. Since the inorganic coating film hardens while glass is the main component, it has excellent impact resistance and corrosion resistance, and can maintain the coated state on the surface of the article for a long period of time, thereby protecting the surface of the article.

[0020] The spherical space is formed by nanobubbles, and the average diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90The inorganic coating film in which nanobubbles of the above are dispersed (dispersed and dissolved) at a specified concentration inside the inorganic coating film has nanobubbles of average diameter D 90 By dispersing nanobubbles of less than 1 μm at a predetermined concentration, the proportion of the inorganic coating film itself per unit area of ​​the inorganic coating film can be reduced by the nanobubbles, which are ultrafine bubbles, and the amount of the inorganic coating film itself when the surface of the article to be coated is reduced, and the amount of the inorganic coating film coated on the article can be reduced. In addition, compared to when the inorganic coating film does not have nanobubbles dispersed therein, the reduced amount of coverage reduces the unit price of the coating film per unit area of ​​the surface of the article, and the surface of the article can be coated inexpensively with the inorganic coating film. Since the mass per unit area of ​​the inorganic coating film is reduced compared to when the inorganic coating film does not have nanobubbles dispersed therein (dispersed and dissolved), when the inorganic coating film covers the surface of the article to be coated, the increase in the weight of the article including the inorganic coating film can be minimized. Even if the inorganic coating film has nanobubbles, which are ultrafine bubbles, dispersed therein (dispersed and dissolved), it hardens in a state where glass becomes the main component, so it has excellent impact resistance and corrosion resistance, can maintain the coated state on the surface of the article for a long period of time, and can reliably protect the surface of the article with the inorganic coating film.

[0021] Average diameter of nanobubbles D 50 is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 The inorganic coating film in which nanobubbles of the above are dispersed and mixed at a specified concentration inside the inorganic coating film has an average particle size of D 50Since nanobubbles having a size of 1 nm or more and less than 500 nm are dispersed and mixed in a large amount at a predetermined concentration inside the inorganic coating film, the proportion of the inorganic coating film itself per unit area in the inorganic coating film can be reduced by the nanobubbles, which are ultrafine bubbles, and the coating amount of the inorganic coating film itself when the inorganic coating film coats the surface of the article to be coated can be reliably reduced. In addition, the reduction in the coating amount reduces the unit price of the inorganic coating film per unit area of ​​the surface of the article, and the surface of the article can be coated with the inorganic coating film at low cost.

[0022] In an inorganic coating film having a nanobubble content in the range of 10 to 95 vol. %, the content of the nanobubbles in the inorganic coating film in which the nanobubbles are dispersed is in the above range, so that ultrafine nanobubbles are dispersed and mixed in a large amount at a predetermined concentration inside the inorganic coating film, and the proportion of the inorganic coating film itself per unit area in the inorganic coating film can be reliably reduced by the ultrafine nanobubbles, and the amount of the inorganic coating film itself coated on the surface of the article to be coated can be reliably reduced. In addition, the reduced amount of coating reduces the unit price of the inorganic coating film per unit area of ​​the surface of the article, making it possible to coat the surface of the article with the inorganic coating film at low cost.

[0023] In an inorganic coating film in which the gas forming nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them, a large number of nanobubbles (spherical spaces) of ultrafine bubbles made from the example gases or mixed gases of these gases are dispersed and mixed (dispersed and dissolved) inside the inorganic coating film, and the proportion of the inorganic coating film itself per unit area of ​​the inorganic coating film can be reliably reduced by the ultrafine nanobubbles (spherical spaces). This reduces the amount of the inorganic coating film itself coated when the inorganic coating film coats the surface of the article to be coated, and the amount of the inorganic coating film coated on the article can be reduced. Furthermore, the reduced amount of coating reduces the unit price of the inorganic coating film per unit area of ​​the surface of the article, and the surface of the article can be coated with the inorganic coating film at low cost.

[0024] According to the coating liquid of the present invention, a liquid silicon material consisting of at least one of polysilazane and siloxane, an alkyl silicate condensate, and an inert organic solvent are mixed at a predetermined mixing ratio, and a large number of independent fine spherical spaces are dispersed and mixed (dispersed and dissolved) inside the coating liquid, so that the ratio of the coating liquid itself per unit volume of the coating liquid can be reduced by the large number of fine spherical spaces, and the coating amount of the coating liquid itself is reduced when the coating liquid for forming an inorganic coating film is coated on the surface of the object to be coated, and the coating amount of the coating liquid on the object can be reduced, and the unit price of the coating liquid per unit area of ​​the surface of the object can be reduced by reducing the coating amount compared to when the spherical spaces are not dispersed and mixed in the coating liquid, and the coating liquid can be used inexpensively. Compared to when the spherical spaces are not dispersed and mixed in the coating liquid, the mass per unit volume of the coating liquid is reduced, so that when the coating liquid is coated on the surface of the object to be coated, the increase in weight of the object including the inorganic coating film formed (film-formed) from the coating liquid can be minimized. For example, when the article to be coated with the coating liquid is an automobile, the weight increase of the automobile including the inorganic coating film made from the coating liquid can be minimized, and the fuel efficiency and acceleration performance of the automobile can be prevented from being deteriorated. The coating liquid forms a coating layer of an organic composite structure in which an organic functional group is linked as a side chain to a part of the main chain by a siloxane bond by reacting with polysilazane or siloxane with moisture, and the alkyl silicate condensate acts as a crosslinking agent to form a crosslinked structure in the coating layer, so that the elastic modulus of the inorganic coating film made from the coating liquid can be reduced, and the inorganic coating film made from the coating liquid can maintain its flexibility even if it has a thickness of a certain level or more. The coating liquid can make the inorganic coating film made from the coating liquid follow the deformation of the article to be coated, and can prevent the occurrence of cracks and peeling in the inorganic coating film, and can form an inorganic coating film having high impact resistance and high corrosion resistance on the surface of the article to be coated.The coating liquid hardens the inorganic coating film made from it in a state where glass is the main component, so the inorganic coating film has excellent impact resistance and corrosion resistance and can maintain the coated state on the surface of the article for a long period of time, and the inorganic coating film can protect the surface of the article.

[0025] The spherical space is formed by nanobubbles, and the average diameter of the nanobubbles is D 90 is less than 1 μm, and its average particle size D 90 The coating liquid in which nanobubbles of the above are dispersed (dispersed and dissolved) at a certain concentration has an average particle size of D 90 By dispersing and mixing nanobubbles having a size of less than 1 μm at a predetermined concentration, the proportion of the coating liquid itself per unit volume of the coating liquid can be reduced by the nanobubbles, and the amount of the coating liquid itself when coated on the surface of the article to be coated can be reduced, and the amount of the coating liquid on the article can be reduced. In addition, the unit price of the coating liquid per unit area of ​​the surface of the article can be reduced by the reduction in the amount of coating compared to when nanobubbles are not dispersed in the coating liquid, and the coating liquid can be used at a low cost. Since the mass per unit volume of the coating liquid is reduced compared to when nanobubbles are not dispersed in it, when the coating liquid is coated on the surface of the article to be coated, the increase in the weight of the article including the inorganic coating film formed from the coating liquid can be minimized. Even if the inorganic coating film made from the coating liquid contains nanobubbles, which are ultrafine bubbles, dispersed (dispersed and dissolved), the coating liquid hardens in a state where glass is the main component, so that the inorganic coating film made from the coating liquid has excellent impact resistance and corrosion resistance and can maintain the coating state on the surface of the article for a long period of time, and the inorganic coating film can reliably protect the surface of the article.

[0026] The negatively charged nanobubbles are dispersed and mixed into the coating liquid, and the average diameter of the nanobubbles D 50is in the range of 1 nm or more and less than 500 nm, and its average particle size D 50 In a coating liquid in which the nanobubbles are dispersed and mixed in at a predetermined concentration, the nanobubbles dispersed and mixed in the coating liquid repel each other and do not bond (coalesce) with each other because the nanobubbles are negatively charged, and the nanobubbles are prevented from bonding together and becoming large bubbles, and the state in which the ultrafine bubbles are dispersed and mixed in the coating liquid that forms the inorganic coating film can be maintained. Since the ultrafine bubbles are dispersed and mixed in the coating liquid (dispersed and dissolved) without bonding together, the nanobubbles are unlikely to volatilize from the coating liquid and can remain in the coating liquid for a long period of time. The coating liquid contains nanobubbles having an average particle size D in the above range. 50 Since a large amount of nanobubbles are dispersed and mixed (dispersed and dissolved) at a predetermined concentration, the proportion of the coating liquid itself per unit volume in the coating liquid can be reduced by the nanobubbles, which are ultrafine bubbles, and the coating amount of the coating liquid itself can be reliably reduced when coating the surface of an article to be coated with the coating liquid that forms an inorganic coating film.

[0027] In a coating liquid having a nanobubble content in the range of 10 to 95 vol.%, the nanobubble content in the coating liquid is in the above range, and a large amount of ultrafine nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration, and the proportion of the coating liquid itself per unit volume in the coating liquid can be reduced by the ultrafine nanobubbles, and the coating amount of the coating liquid itself can be reliably reduced when coating the coating liquid on the surface of the article to be coated. Furthermore, the reduced coating amount reduces the unit price of the coating liquid per unit area of ​​the surface of the article, and the coating liquid for forming the inorganic coating film can be used inexpensively.

[0028] The blending ratio of the silicon material to the total mass of the coating liquid before nanobubbles are mixed is in the range of 30 to 60 wt%, the blending ratio of the alkyl silicate condensate to the total mass of the coating liquid before nanobubbles are mixed is in the range of 10 to 15 wt%, the blending ratio of the inert organic solvent to the total mass of the coating liquid before nanobubbles are mixed is in the range of 30 to 60 wt%, the viscosity of the coating liquid at 20°C in which the nanobubbles are dispersed and mixed is in the range of 0.98 to 1.008 mPa s, and the rising speed of the nanobubbles inside the coating liquid at 20°C in which the nanobubbles are dispersed and mixed is In the coating liquid in the range of 0·000015~0.00005mm / min, the viscosity of the coating liquid in which nanobubbles are dispersed (dispersed and dissolved) at 20°C is within the above range, and the rising speed of nanobubbles in the coating liquid in which nanobubbles are dispersed is within the above range, so that the nanobubbles are less likely to volatilize from the coating liquid and the nanobubbles can be made to remain in the coating liquid for a long period of time, and the amount of coating liquid itself can be reliably reduced when coating the coating liquid for forming an inorganic coating film on an article to be coated. Since the coating liquid has a blending ratio of the silicon material within the above range, the inorganic coating film made from the coating liquid is formed to a predetermined thickness, and an inorganic coating film having high impact resistance and high corrosion resistance can be formed on the surface of the article to be coated. Since the coating liquid has a blending ratio of the alkyl silicate condensate within the above range, the formation speed of the inorganic coating film made from the coating liquid can be accurately controlled.

[0029] In a coating liquid in which the gas forming nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them, a large number of nanobubbles (spherical spaces) of ultrafine bubbles made from the exemplified gases or mixed gases of these gases are dispersed and mixed (dispersed and dissolved) inside the coating liquid, and the proportion of the coating liquid itself per unit volume of the coating liquid can be reduced by the ultrafine nanobubbles (spherical spaces). When the coating liquid for forming an inorganic coating film is coated on the surface of an article to be coated, the coating amount of the coating liquid itself is reduced, and the coating amount of the coating liquid on the article can be reduced. At the same time, the reduced coating amount reduces the unit price of the coating liquid per unit area of ​​the surface of the article, and the coating liquid can be used inexpensively. [Brief description of the drawings]

[0030] [Figure 1] FIG. 1 is a configuration diagram showing an example of a nanobubble generating device that mixes nanobubbles into a coating liquid. [Diagram 2] 1A to 1C are cross-sectional views for explaining, in chronological order, the mechanism by which an inorganic coating film is formed from a coating liquid on the surface of an article coated with the coating liquid. [Diagram 3] FIG. 2 is a conceptual diagram showing an example of the structure of an inorganic coating film. [Figure 4] A diagram illustrating the nanobubbles present (dissolved) inside an inorganic coating film. [Diagram 5] FIG. 1 is a graph showing the correlation between the thickness of an inorganic coating film and the impact resistance and corrosion resistance. [Figure 6] FIG. 2 is a diagram showing the blend ratio, porosity, total number of nanobubbles, and nanobubble particle size of the coating liquids of Samples A to E and the inorganic coating films made from the coating liquids of Samples A to E. [Figure 7] FIG. 2 shows the blend ratio, porosity, total number of nanobubbles, and nanobubble diameter of the coating liquids of Samples F to H and the inorganic coating films made from the coating liquids of Samples F to H. [Figure 8] 1 is a graph showing the evaluation of flexibility, impact resistance, and corrosion resistance of inorganic coating films made from the coating liquids of samples A to E. [Figure 9] Graph showing evaluation of flexibility, impact resistance, and corrosion resistance of inorganic coating films made from the coating liquids of Samples F to H. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] The coating liquid and inorganic coating film according to the present invention will be described in detail with reference to the attached drawings. FIG. 1 is a configuration diagram showing an example of a nanobubble generator 20 for mixing nanobubbles 14 into a coating liquid 10, and (a) to (c) of FIG. 2 are cross-sectional views for explaining in a time series manner the mechanism by which an inorganic coating film 13 is formed from the coating liquid 10 on a surface 12 (front and back) of an article 11 coated (applied) with the coating liquid 10. FIG. 3 is an image diagram showing an example of the structure of the inorganic coating film 13, and FIG. 4 is a diagram illustrating an image of nanobubbles 14 dispersed and mixed (dispersed and dissolved) inside the inorganic coating film 13. FIG. 5 is a diagram illustrating the correlation between the film thickness of the inorganic coating film 13 and the impact resistance and corrosion resistance. In FIG. 4, the nanobubbles 14 are illustrated as an image that can be seen with the naked eye, but in reality, the nanobubbles 14 cannot be seen with the naked eye.

[0032] (Coating Liquid 10) The coating liquid 10 is coated (applied) onto a surface 12 (front and back) of an article 11 to be coated. The hardened coating liquid 10 forms an inorganic coating film 13 that covers the surface 12 of the article 11. The raw materials for the coating liquid 10 include a liquid organosilicon material (silicon material) made of at least one of polysilazane (inorganic polysilazane, organic polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent. Inside (within) the coating liquid 10, particles having an average particle size D 90 Nanobubbles 14 (ultrafine bubbles) (numerous independent tiny spherical spaces) with sizes less than 1 μm are dispersed and mixed (dispersed and dissolved) at a specified concentration.

[0033] Either one of polysilazane and siloxane (polymeric silane) may be used, or a mixture of both may be used. An organosilicon material, an alkylsilicate condensate, and an inert organic solvent are mixed and stirred at a predetermined ratio to produce the coating liquid 10. In the coating liquid 10, an organosilicon material consisting of at least one of polysilazane and siloxane, and an alkylsilicate condensate are diluted with an inert organic solvent.

[0034] The inorganic polysilazane used is Si-N perhydropolysilazane. As the polysilazane, Si-CN organopolysilazane, Si-C polycarbosilane, SiC-O, Si-BCN, and Si-Ti-N can also be used. Organopolysiloxane can also be used.

[0035] As the organic polysilazane, modified polysilazanes such as methylpolysilazane, dimethylpolysilazane, phenylpolysilazane, vinylpolysilazane, etc. can also be used. Also usable is a crosslinked polysilazane that is chemically crosslinked with a compound such as a hydrocarbon compound having a reactive group such as a hydroxyl group, a vinyl group, an amino group, or a silyl group that chemically reacts with polysilazane to form a crosslinked structure, a cyclic saturated hydrocarbon compound, a cyclic unsaturated hydrocarbon compound, a saturated heterocyclic compound, an unsaturated heterocyclic compound, or a silicone compound.

[0036] In addition, polyborosilazane, inorganic silazane high polymers or modified polysilazanes, copolymerized silazanes, low-temperature ceramicized polysilazanes obtained by adding or incorporating a catalytic compound to polysilazane to promote ceramicization, silicon alkoxide-added polysilazanes, glycidol-added polysilazanes, acetylacetonato complex-added polysilazanes, metal carboxylate-added polysilazanes, and polysilazane compositions obtained by adding amines and / or acids to the above-mentioned various polysilazanes or modified products can also be used.

[0037] The polysilazane may be one type of single polysilazane, a mixture of two or more types of polysilazanes selected from various polysilazanes, or a polysilazane copolymer consisting of two or more types of polysilazane structures, and contains at least one hydrogen atom directly bonded to a silicon atom in one molecule. The polysilazane forming the coating liquid 10 has a weight average molecular weight in the range of 100 to 100,000,000, preferably 1,000 to 1,000,000, and more preferably 2,000 to 500,000, from the viewpoints of solubility in a solvent and workability during application. If the weight average molecular weight is 100 or more, the volatility is low, and the polysilazane itself volatilizes during the volatilization of the solvent and the curing process, which may deteriorate the film quality of the coating film.

[0038] The inorganic polysilazane is represented by the general formula (Chemical Formula 1).

[0039] [ka] Inorganic polysilazanes include linear structures having structural units, have a molecular weight of 690 to 2,000, and contain 3 to 10 SiH groups in one molecule. 3 groups and have element ratios by weight of Si: 59-61, N: 31-34, and H: 6.5-7.5 as determined by chemical analysis; and perhydropolysilazane having a polystyrene-equivalent average molecular weight in the range of 3,000 to 20,000.

[0040] Perhydropolysilazane contains chain and cyclic portions in its molecule and is represented by the following chemical formula (Chemical Formula 2).

[0041] [ka] An example of the structure of perhydropolysilazane is represented by the following chemical formula (Chemical Formula 3).

[0042] [ka] Another example of the perhydropolysilazane compound group is represented by the following general formula (Chemical Formula 4), which has a Si-N bond and a functional group (R 1 ~R 3 ), and -(SiR 1 R 2 -NR 3 )-units, and has a functional group R that is directly bonded to Si. 1 ,R 2 At least one of the above is an organic polymer formed from an organic functional group such as an alkyl group having carbon (C).

[0043] [ka] Perhydropolysilazane is a functional group (R 1 ~R 3 ) is a methyl group (CH 3 ) content is 50% or more. Perhydropolysilazane is a compound that contains one type of -(SiR 1 R2 -NR 3 )-units, as well as polymers formed from functional groups (R 1 ~R 3 ) with different compositions 1 R 2 -NR 3 The perhydropolysilazane may be a polymer formed from R 1 , R 2 , R 3 represents a hydrogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an aryl group, or a group other than these groups in which the group directly bonded to silicon is carbon, an alkylsilyl group, an alkylamino group, or an alkoxy group. 1 , R 2 , R 3 At least one of is a hydrogen atom.

[0044] As an example, perhydropolysilazane (A) is represented by the following general formula (Chemical Formula 5): -(SiH(CH 3 )-NH)- unit, -(Si(CH 3 )2-NH)- unit, -(SiR 1 (CH 3 )-NR 3 )-units. 1 (CH 3 )-NR 3 The functional group R1 in the -unit is H or CH 3 and the functional group R3 directly bonded to N is an organic functional group that promotes the reaction. By including perhydropolysilazane (A) in the coating liquid 10, the reaction after the coating liquid 10 is applied to the surface 12 of the article 11 is promoted, and an organic / inorganic hybrid coating film 13 can be formed on the surface 12 of the article 11 at an early stage.

[0045] [ka] Another example of perhydropolysilazane (B) is -(SiH(CH) represented by the following general formula (Chemical Formula 6). 3 )-NH)- unit, -(SiR 1 (CH 3 )-NH)- units, and 1 (CH 3 Functional group R of the -NH)- unit 1 is an organic functional group that realizes high heat resistance. By including perhydropolysilazane (B) in the coating liquid 10, the heat resistance of the organic / inorganic hybrid coating film 13 that covers the surface 12 of the article 11 can be improved.

[0046] [ka] The perhydropolysilazane contained in the coating liquid 10 may be a mixture of multiple types of perhydropolysilazanes having different polymer structures. For example, perhydropolysilazane may be a mixture of perhydropolysilazane (A) and perhydropolysilazane (B). According to a mixing experiment of these perhydropolysilazane (A) and perhydropolysilazane (B), it was confirmed that a mixture of 50 mass% perhydropolysilazane (A) and 50 mass% perhydropolysilazane (B) exhibited rust prevention properties equal to or greater than that of perhydropolysilazane (A) alone, and also reduced the curing time (time to generate organic / inorganic hybrid coating film 13) compared to perhydropolysilazane (B) alone.

[0047] Organopolysilazane is represented by the general formula (4) above, 1 and R 2 A hydrogen atom, R 3 -(R 2 Polysilazane having a cyclic structure with a degree of polymerization of 3 to 5, (R 3 SiHNH) x (R 2 SiH) 1.5 N] 1-XA polysilazane having both a chain structure and a cyclic structure in a molecule represented by the chemical formula (0.4 < X < 1), and in the above general formula (Chemical Formula 4), R 1 is a hydrogen atom, R 2 , R 3 is a polysilazane having an organic group, R 1 and R 2 have an organic group, R 3 has a hydrogen atom and -(R 1 R 2 SiNR 3 )- as a repeating unit, and there is a polysilazane mainly having a cyclic structure with a degree of polymerization of 3 to 5.

[0048] For example, an organopolysilazane having a cross-linked structure in the molecule other than the above general formula (Chemical Formula 4) is represented by the following general formula (Chemical Formula 7).

[0049]

Chemical Formula

[0050]

Chemical Formula

[0051] Examples of the monovalent ethylenically unsaturated group include alkenyl groups such as vinyl, allyl, butenyl, pentenyl, and hexenyl. The number of carbon atoms in the alkenyl group is preferably 2 to 8, more preferably 2 to 6, and even more preferably 2 to 3. Examples of the monovalent ethylenically unsaturated group include (meth)acryloyloxyalkyl groups, that is, groups represented by the formula (B): -R 12 -OC(=O)-CR 11 =CH 2 Specifically, there are acryloyloxypropyl groups and methacryloyloxypropyl groups. 11 is a hydrogen atom or a methyl group, R 12 is an alkanediyl group, preferably an alkanediyl group having from 1 to 5 carbon atoms. Incidentally, (meth)acrylic is used as a general term for acrylic and methacrylic, and (meth)acryloyl is used as a general term for acryloyl and methacryloyl.

[0052] In the monovalent ethylenically unsaturated group, an alkenyl group is preferred, a vinyl group and an allyl group are preferred, and a vinyl group is more preferred. Examples of the monovalent hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl and heptyl groups; aryl groups such as phenyl, tolyl and xylyl groups; and aralkyl groups such as benzyl and phenethyl groups. The number of carbon atoms in the monovalent hydrocarbon group is preferably 1 or more and 8 or less, more preferably 1 or more and 5 or less, and even more preferably 1 or more and 3 or less.

[0053] An example of a monovalent substituted hydrocarbon group is a 3-mercaptopropyl group (-(CH 2 ) 3 -SH) and 3-aminopropyl group (-(CH 2 ) 3 -NH 2 ) is available. 1 From the viewpoint of fine particle formation, each of them is preferably independently an alkyl group or an alkenyl group, more preferably, each of them is independently an alkyl group having 1 to 3 carbon atoms, a vinyl group, or an allyl group, and even more preferably, a methyl group or a vinyl group.

[0054] In one molecule of the organopolysiloxane having the average unit formula (A), at least a portion of R 1 is a group containing a functional group (L) such as a monovalent ethylenically unsaturated group, an aryl group, or an aralkyl group, and is preferably a monovalent ethylenically unsaturated group, and more preferably an alkenyl group. The total proportion of the monovalent ethylenically unsaturated group, the aryl group, or the aralkyl group is determined based on the total R 1 Based on this, it is preferably 50 mol % or more, more preferably 60 mol % or more, even more preferably 70 mol % or more, still more preferably 80 mol % or more, and particularly preferably 90 mol % or more. The monovalent ethylenically unsaturated group, aryl group, or aralkyl group is a hydrophobic group containing a nonionic functional group capable of coordinating to a metal ion.

[0055] In the average unit formula (A), a, b, c, and d represent each constituent unit (R 1 3SiO 1 / 2 ), (R 1 2 SiO 2 / 2 ), (R 1 SiO 3 / 2 ) and (SiO 4 / 2 The sum of the mole fractions of each structural unit, a, b, c, and d, is 1. a is R 1 3 SiO 1 / 2 a is the molar fraction of siloxane units represented by (M units). a is from 0 to 0.5, preferably 0.4 or less, more preferably 0.3 or less, even more preferably 0.2 or less, and particularly preferably 0.1 or less.

[0056] b is R 1 2 SiO 2 / 2 is the mole fraction of siloxane units represented by (D units). b is 0 or more and 0.5 or less, preferably 0.4 or less, more preferably 0.3 or less, further preferably 0.2 or less, and particularly preferably 0.1 or less. c is R 1 SiO 3 / 2 is the mole fraction of siloxane units represented by (T units). c is 0.3 or more and 1 or less, preferably 0.4 or more, 0.5 or more, or 0.6 or more, more preferably 0.7 or more, still more preferably 0.8 or more, and particularly preferably 0.9 or more.

[0057] d is SiO 4 / 2 is the mole fraction of siloxane units represented by (Q units). d is 0 or more and 0.7 or less, preferably 0.6 or less, 0.5 or less, or 0.4 or less, more preferably 0.3 or less, even more preferably 0.2 or less, and particularly preferably 0.1 or less. The sum of c and d, which indicates the total of branched constitutional units, is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.8 or more, and particularly preferably 0.9 or more.

[0058] The organopolysiloxane is a polymer having a constitutional unit (R 1 3 SiO 1 / 2In the case where the structural unit (R 1 2 SiO 2 / 2 ) and (R 1 SiO 3 / 2 The same applies to the R 1 At least part of R 2 In the average unit formula (A), R may have a structural unit replaced with O. 2 is a hydrogen atom or an alkyl group. 2 O represents a hydroxyl group or an alkoxy group bonded to a silicon atom contained in the organopolysiloxane skeleton. Examples of the alkyl group include a methyl group, an ethyl group, and a propyl group. The number of carbon atoms in the alkyl group is preferably 1 or more and 3 or less.

[0059] The above R in each of the structural units 1 At least part of R 2 The amount of the structural unit replaced with O is preferably 0 or more and 0.10 or less, more preferably 0 or more and 0.05 or less, and even more preferably 0 or more and 0.03 or less, relative to the sum of the molar fractions of the structural units, a, b, c, and d, which is 1. The alkoxy group in the structural unit is, for example, an alkoxy group that is a hydrolyzable group contained in an alkoxysilane described later, and remains in the molecule without being hydrolyzed or polycondensed. The hydroxy group in this structural unit is, for example, a hydroxy group that remains in the molecule after the alkoxy group is hydrolyzed without being polycondensed.

[0060] The organopolysiloxane is preferably a silsesquioxane. Silsesquioxane is a polymer having a main chain structure composed of Si-O bonds and a main structural unit (R 1 SiO 3 / 2) units, and the c is 0.7 or more. Examples of the silsesquioxane structure include a random structure, a complete cage structure, an incomplete cage structure, and a ladder structure. Among these, silsesquioxanes having a random structure are preferred from the viewpoint of ease of production.

[0061] The structural unit (R 1 3 SiO 1 / 2 As the alkoxysilane that forms R 1 3 Si(OR 2 Specific examples thereof include methoxydimethylvinylsilane, ethoxydimethylvinylsilane, methoxydimethylphenylsilane, and ethoxydimethylphenylsilane; and methoxytrimethylsilane and ethoxytrimethylsilane.

[0062] The structural unit (R 1 2 SiO 2 / 2 As the alkoxysilane that forms R 1 2 Si(OR 2 ) 2 Specific examples thereof include dimethoxymethylvinylsilane, diethoxymethylvinylsilane, and dimethoxybenzylmethylsilane; as well as dimethoxydimethylsilane, dimethoxydiethylsilane, diethoxydimethylsilane, diethoxydiethylsilane, dipropoxydimethylsilane, and dipropoxydiethylsilane.

[0063] The structural unit (R 1 SiO 3 / 2 As the alkoxysilane that forms R 1 Si(OR 2 ) 3Specific examples thereof include trimethoxyvinylsilane, triethoxyvinylsilane, trimethoxyallylsilane, triethoxyallylsilane, (3-(meth)acryloyloxypropyl)trimethoxysilane, and (3-(meth)acryloyloxypropyl)triethoxysilane; as well as methyltrimethoxysilane, methyltriethoxysilane, methyltrippropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, and butyltrimethoxysilane. The structural unit (SiO 4 / 2 As the alkoxysilane that forms Si(OR 2 ) 4 Specific examples of the compound include tetramethoxysilane, tetraethoxysilane, and tetrapropoxysilane.

[0064] The siloxane contained in the coating liquid 10 may be any one of a chain siloxane having a chain skeleton and a cyclic siloxane having a cyclic skeleton, or a mixture of two or more of them. As the cyclic siloxane, hexamethylcyclotrisiloxane (C 6 H 18 O 3 S 4 ), Octamethylcyclotetrasiloxane (C 6 H 24 O 4 S 4 ), Decamethylcyclopentasiloxane (C 10 H 30 O 5 S 5 ) or a mixture of two or more of them can be used. The number average molecular weight of polysilazane and siloxane is in the range of 3000 to 150000 g / mol.

[0065] The alkyl silicate condensate is one selected from tetramethyl orthosilicate, tetraethyl orthosilicate, tetra-n-propyl orthosilicate, tetra-i-propyl orthosilicate, tetra-n-butyl orthosilicate, tetra-sec-butyl orthosilicate, methyl polysilicate, and ethyl polysilicate, or a condensate (mixture) of two or more of them. The inert organic solvent is inert to the organic polysilazane and siloxane as well as the alkyl silicate condensate, and is selected from dibutyl ether, turpentine oil, benzene, and toluene.

[0066] Since the number average molecular weight of the polysilazane (perhydropolysilazane, organopolysilazane, organopolysiloxane, etc.) or siloxane in the coating liquid 10 is within the above range, the coating liquid 10 containing the polysilazane and / or polysiloxane can maintain a predetermined viscosity, and an inorganic coating film 13 with a predetermined thickness can be formed from the coating liquid 10. Since the coating liquid 10 is coated on the surface 12 of the article 11 to be coated while maintaining a predetermined viscosity, even if the coating liquid 10 is coated on the surface 12 of the article 11 on which minute holes or meshes are formed, the coating liquid 10 does not permeate into the inside of the article 11, and an inorganic coating film 13 with a substantially uniform thickness can be formed on the surface 12 of the article 11.

[0067] In the coating liquid 10, the mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid before nanobubbles are mixed is in the range of 30 to 60 mass%, the mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid before nanobubbles are mixed is in the range of 10 to 15 mass%, and the mixing ratio of the inert organic solvent to the total mass of the coating liquid before nanobubbles are mixed is in the range of 30 to 60 mass%. If the mixing ratio of the organosilicon material (polysilazane, siloxane) is less than 30 mass%, the content of the organosilicon material is low, and it is not possible to form an inorganic coating film 13 of a predetermined thickness having excellent flexibility, impact resistance, and corrosion resistance on the surface 12 of the article 11. If the mixing ratio of the organosilicon material (polysilazane, siloxane) exceeds 60 mass%, the viscosity of the coating liquid 10 increases, and nanobubbles 14 described below cannot be dispersed and mixed (dispersed and dissolved) in the coating liquid 10 at a predetermined concentration. Since the mixing ratio of the organosilicon material (polysilazane, siloxane) to the total mass of the coating liquid 10 before the nanobubbles are mixed in falls within the above-mentioned range, by using the coating liquid 10 after the nanobubbles have been mixed in, it is possible to produce an inorganic coating film 13 of an appropriate thickness in which the nanobubbles 14 are dispersed and mixed (dissolved) at a predetermined density and which has excellent flexibility, impact resistance, and corrosion resistance.

[0068] If the mixing ratio of the alkyl silicate condensate is less than 10 mass%, the alkyl silicate condensate has a weak effect as a crosslinking agent, and a sufficient crosslinked structure is not formed in the inorganic coating film 13. If the mixing ratio of the alkyl silicate condensate exceeds 15 mass%, an unnecessary crosslinked structure is formed in the inorganic coating film 13, and the flexibility of the inorganic coating film 13 becomes greater than necessary. Since the mixing ratio of the alkyl silicate condensate to the total mass before the nanobubbles are mixed in the coating liquid 10 is within the above range, it is possible to use the coating liquid 10 after the nanobubbles are mixed in to produce an inorganic coating film 13 having an appropriate crosslinked structure and appropriate flexibility, and in which the nanobubbles are dispersed and mixed at a predetermined density.

[0069] If the blending ratio of the inert organic solvent is less than 30% by mass, the viscosity of the coating liquid 10 becomes high, and the nanobubbles 14 cannot be dispersed (dissolved) at a predetermined concentration inside the coating liquid 10. If the blending ratio of the inert organic solvent exceeds 60% by mass, the viscosity of the coating liquid 10 becomes lower than necessary, and it is not possible to form an inorganic coating film 13 of a predetermined thickness having excellent flexibility, impact resistance, and corrosion resistance on the surface 12 of the article 11. Since the blending ratio of the inert organic solvent to the total mass of the coating liquid before nanobubbles are mixed in is within the above range, the coating liquid 10 after nanobubbles are mixed in can be used to create an inorganic coating film 13 of appropriate viscosity in which the nanobubbles 14 are dispersed (dissolved) at a predetermined density and which has excellent flexibility, impact resistance, and corrosion resistance.

[0070] The coating liquid 10 contains 30 to 60 mass % of the organosilicon material (polysilazane and / or siloxane) and 10 to 15 mass % of the alkylsilicate condensate relative to the total mass of the coating liquid before nanobubbles are mixed in, so that the rate of formation of the inorganic coating film 13 made from the coating liquid 10 can be appropriately controlled. Specifically, the hydrolysis of the alkylsilicate condensate proceeds faster than the condensation of the polysilazane and / or siloxane, so that some water (H 2 O) is consumed first, the progress of the condensation reaction of polysilazane and / or siloxane can be delayed, and the rate of formation of the inorganic coating film 13 can be controlled. In addition, since the hydrolysis of the alkyl silicate condensate occurs first, a crosslinked structure can be reliably formed in the inorganic coating film 13, thereby imparting flexibility to the inorganic coating film 13.

[0071] In addition, since the organic solvent is selected from dibutyl ether, turpentine oil, benzene, and toluene, which are inactive to organic polysilazane, siloxane, and alkyl silicate condensates, the condensation reaction of organic polysilazane and / or siloxane does not progress rapidly, and the rate of formation of the inorganic coating film 13 can be appropriately controlled. The coating liquid 10 capable of controlling the rate of formation of the inorganic coating film 13 allows easy coating of the surface 12 of the article 11.

[0072] (Nanobubble mixing device 15) As shown in Fig. 1, an example of the nanobubble mixing device 15 is composed of a coating liquid storage tank 16 having a predetermined volume, a gas supply tank 17, a water supply pump 18, an air supply pump 19, a static fluid mixer 20 (nanobubble generator), a coating liquid storage tank 21 having a predetermined volume and storing the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed, a cooling device (not shown), and a controller (not shown). The nanobubble mixing device 15 is supplied with power from a power source (not shown). The coating liquid storage tank 16 stores the coating liquid 10 (the coating liquid 10 before the nanobubbles 14 are dispersed and mixed) in which the liquid organosilicon material made of at least one of the above-mentioned polysilazane and siloxane, the alkyl silicate condensate, and the inert organic solvent are mixed and stirred at a predetermined mixing ratio.

[0073] A level gauge (not shown) is installed in the coating liquid storage tank 16. The level gauge is connected to the controller via a signal line, measures the level (storage amount) of the coating liquid 10 stored in the coating liquid storage tank 16, and transmits the measured level to the controller. The coating liquid storage tank 16 is connected to a water supply pump 18 via a water supply pipe 22 (water supply pipe). Although not shown, a flow meter, a check valve, and a water supply solenoid valve are installed in the water supply pipe 22. The flow meter is connected to the controller via a signal line, measures the flow rate of the coating liquid 10 flowing through the water supply pipe 22, and transmits the measured flow rate to the controller. A control unit of the water supply solenoid valve is connected to the controller via a signal line, and its start / stop (open / close) is controlled by the controller.

[0074] The gas supply tank 17 contains a gas to be dispersed and mixed into the coating liquid 10 at a predetermined pressure. The gas to be dispersed and mixed into the coating liquid 10 may be any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them. The gas supply tank 17 is connected to a mixing pipe 24 (mixing pipe) via an air supply pipe 23 (air supply pipe). Although not shown, a barometer, a check valve, and an air supply solenoid valve are installed in the air supply pipe 23. The barometer is connected to a controller via a signal line, measures the air pressure of the gas contained in the gas supply tank 17, and transmits the measured air pressure to the controller. The control unit of the air supply solenoid valve is connected to the controller via a signal line, and its on / off (opening / closing) is controlled by the controller. An air supply pump 19 is installed in the air supply pipe 23. The control unit of the air supply pump 19 is connected to the controller via a signal line. The on / off and output of the air supply pump 19 are controlled by the controller.

[0075] The water supply pump 18 is installed in a water supply pipe 22, and its control unit is connected to the controller via a signal line. The start / stop and output of the water supply pump 18 are controlled by the controller. The water supply pump 18 is connected to a static fluid mixer 20 via a mixing pipe 24. The static fluid mixer 20 is connected to a coating liquid storage tank 21 of a predetermined volume via a supply pipe 25. A level meter (not shown) is installed in the coating liquid storage tank 21. The level meter is connected to the controller via a signal line, measures the level (storage volume) of the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed and stored in the coating liquid storage tank 21, and transmits the measured level to the controller.

[0076] The static fluid mixer 20 (nanobubble generator) is formed of a cylindrical unit 26 having an inlet and an outlet, and a plurality of honeycomb structure elements (agitation blades) (not shown) arranged inside the cylindrical unit 26. The honeycomb structure elements are arranged in a state of being connected in series inside the cylindrical unit 26. The static fluid mixer 20 (nanobubble generator) passes the coating liquid 10 and gas through the inside of the honeycomb structure element by centrifugal force generated by high-speed rotation, and generates nanobubbles 14 by ultra-finely dividing the gas into nano-level particles, while uniformly mixing (dissolving) the generated nanobubbles 14 into the coating liquid 10, thereby creating a coating liquid 10 in which the nanobubbles 14 are uniformly dispersed and mixed (dispersed and dissolved) throughout. In the static fluid mixer 20, the coating liquid 10 and the gas pass through the inside of the honeycomb structure element many times, thereby proceeding with ultra-finely dividing the gas (to nano-level) and mixing (dissolving) the ultra-finely divided gas into the coating liquid 10. The cooling device cools the cylindrical unit 26 of the static fluid mixer 20 to a set temperature by circulating a refrigerant (e.g., hydrofluorocarbon). The control unit of the cooling device is connected to the controller via a signal line. The start / stop and output of the cooling device are controlled by the controller.

[0077] The controller is a physical computer that has a central processing unit (CPU or MPU) and memory (main memory and cache memory), runs on an independent operating system (OS), and is equipped with a large-capacity storage area. Input devices such as a keyboard and mouse, and output devices such as a display and printer are connected to the controller via interfaces. The central processing unit of the controller starts a nanobubble mixing application stored in the memory based on the control of the operating system (OS), and performs a mixing operation to disperse and mix (disperse and dissolve) nanobubbles 14 into the coating liquid 10 according to the application.

[0078] When the switch of the nanobubble mixing device 15 is turned on, a mixing operation of mixing nanobubbles 14 into the coating liquid 10 stored in the coating liquid storage tank 16 is started. A predetermined amount of the coating liquid 10 is poured into the coating liquid storage tank 16, and gas (any of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them) is stored at a predetermined pressure in the gas supply tank 17. When the switch of the nanobubble mixing device 15 is turned on, the controller sends a water supply signal to the control unit of the water supply pump 18, sends an air supply signal to the control unit of the air supply pump 19, and sends a cooling signal to the control unit of the cooling device. Furthermore, the controller sends an open signal to the control section of the water supply solenoid valve, sends an open signal to the control section of the air supply solenoid valve, and sends measurement signals to the level meter, flow meter, and barometer.

[0079] The control unit of the water supply pump 18 that has received the water supply signal starts the water supply pump 18 at a predetermined output (set output), and the control unit of the air supply pump 19 that has received the air supply signal starts the air supply pump 19 at a predetermined output (set output). The control unit of the cooling device that has received the cooling signal starts the cooling device at a predetermined output (set output). The control unit of the water supply solenoid valve that has received the open signal opens the water supply solenoid valve, and the control unit of the air supply solenoid valve that has received the open signal opens the air supply solenoid valve. The level meter that has received the measurement signal starts measuring the level of the coating liquid 10 stored in the coating liquid storage tank 16, and the flow meter that has received the measurement signal starts measuring the flow rate of the coating liquid 10 flowing through the water supply pipe 22. The barometer that has received the measurement signal starts measuring the air pressure of the gas flowing through the air supply pipe 23.

[0080] The coating liquid 10 stored in the coating liquid storage tank 16 is forcibly supplied from the coating liquid storage tank 16 to the static fluid mixer 20 by starting the water supply pump 18 (coating liquid water supply step). The coating liquid 10 flows from the water supply pipe 22 through the water supply pump 18 into the mixing pipe 24, and flows into the static fluid mixer 20 through the mixing pipe 24. The gas stored in the gas supply tank 17 is forcibly supplied from the gas supply tank 17 to the static fluid mixer 20 by starting the air supply pump 19 (gas supply step). The gas flows from the air supply pipe 23 through the air supply pump 19 into the mixing pipe 24, is mixed with the coating liquid 10 in the mixing pipe 24, and then flows into the static fluid mixer 20 together with the coating liquid 10. In the mixing pipe 24, the coating liquid supplied by the water supply pump 18 and the gas supplied by the air supply pump 19 are mixed to produce a gas-mixed coating liquid (mixing process). The gas-mixed coating liquid flows into the static fluid mixer 20.

[0081] The controller receives the measured level measured by the level meter of the coating liquid storage tank 16 and outputs (displays) a water injection message on the display when the measured level drops to the water injection level. The water injection message informs the user of the need to inject the coating liquid 10 into the coating liquid storage tank 16. The controller receives the measured flow rate measured by the flow meter and adjusts the output of the water supply pump 18 so that the measured flow rate becomes the target flow rate. The controller receives the measured air pressure measured by the barometer and adjusts the output of the air supply pump 19 so that the measured air pressure becomes the target air pressure.

[0082] The cooling device continuously cools the cylindrical unit 26 of the static fluid mixer 20 using a refrigerant while the nanobubble mixing device 15 is running (cooling process). The cooling device maintains the temperature of the cylindrical unit 26 at a set temperature (for example, 10 to 20°C). In the static fluid mixer 20, the gas-mixed coating liquid 10 mixed with gas flows in from its inlet, and the gas-mixed coating liquid 10 becomes a continuous phase fluid and a dispersed phase fluid by multiple honeycomb structure elements (agitating blades), and the continuous phase and dispersed phase fluids of the gas-mixed coating liquid 10 flow while meandering through the honeycomb structure elements. The fluid (gas) as the dispersed phase is atomized by the shear force received at that time, and a finely atomized mixed fluid is generated.

[0083] Next, the flow of the generated finely divided mixed fluid is rectified, and then the rectified finely divided mixed fluid flows while meandering through the honeycomb structure element arranged on the downstream side, and the finely divided mixed fluid (gas) as the dispersed phase is further refined by the shear force received at that time. Finally, the gas mixed into the coating liquid 10 is ultra-refined to the nano level, and nano-level bubbles (nanobubbles) are dispersed and mixed (dispersed and dissolved) in the coating liquid 10, and particles with an average particle diameter D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm to 500 nm, more preferably, the average particle size D 50A nanobubble-containing coating liquid 10 is produced in which nanobubbles 14 (numerous independent tiny spherical spaces) having a size in the range of 1 nm or more and less than 300 nm are uniformly dispersed and mixed in at a predetermined concentration (nanobubble-containing coating liquid production process).

[0084] When the nanobubbles 14 are mixed into the coating liquid, the temperature of the nanobubble-containing coating liquid 10 in the cylindrical unit 26 in which the nanobubbles are dispersed and mixed rises due to friction between the coating liquid and the nanobubbles 14. However, the cooling device cools the cylindrical unit 26, so that the temperature of the nanobubble-containing coating liquid 10 in the cylindrical unit 26 is maintained at 10 to 20°C. The coating liquid 10 in which the nanobubbles 14 are dispersed and mixed (dispersed and dissolved) is contained in the coating liquid storage tank 21 through the supply pipe 25. The controller receives the measurement level measured by the level meter of the coating liquid storage tank 21 and outputs (displays) the measurement level on a display. The amount of the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed can be known from the measurement level outputted on the display.

[0085] Regarding the method of dispersing and mixing the nanobubbles 14 into the coating liquid 10 (nanobubble generation method), any of the methods involving the flow of the coating liquid 10, such as a swirling liquid flow type, a static mixer type, an ejector type, a Venturi type, or a pressurized dissolution type, may be used, or any of the methods not involving the flow of the coating liquid 10, such as a fine hole type, a rotation type, an ultrasonic type, a steam condensation type, or an electrolysis type, may be used.

[0086] The coating liquid 10 is a mixture of a liquid organosilicon material consisting of at least one of polysilazane and siloxane, an alkyl silicate condensate, and an inert organic solvent at a predetermined mixing ratio, and nanobubbles 14 (a large number of independent minute spherical spaces) are dispersed and mixed (dispersed and dissolved) inside the coating liquid 10. The nanobubbles 14 (spherical spaces) can reduce the proportion of the coating liquid 10 itself per unit volume of the coating liquid 10 (the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed (dispersed and dissolved)), and the coating liquid 10 is thus excellent in coating properties. When the coating liquid 10 (the coating liquid 10 having the nanobubbles 14 dispersed therein (dispersed and dissolved therein)) is coated on the surface 12 of the article 11 to be coated, the amount of the coating liquid 10 itself is reduced, so that the amount of the coating liquid 10 applied to the article 11 can be reduced. In addition, compared to the case where the nanobubbles 14 are not dispersed in the coating liquid 10, the reduced amount of coating reduces the unit cost of the coating liquid 10 per unit area of ​​the surface 12 of the article 11, so that the coating liquid 10 can be used (coated) inexpensively.

[0087] The coating liquid 10 has a reduced mass per unit volume compared to when the nanobubbles 14 (spherical spaces) are not dispersed (dispersed and dissolved) in it, and therefore when the coating liquid 10 is applied to the surface 12 of the article 11 to be coated, it is possible to minimize the increase in weight of the article 11 including the inorganic coating film 13 formed from the coating liquid 10. For example, when the article 11 to be coated with the coating liquid 10 is an automobile, it is possible to minimize the increase in weight of the automobile including the inorganic coating film 13 made from the coating liquid 10, and it is possible to prevent a decrease in the fuel efficiency and acceleration performance of the automobile.

[0088] The nanobubbles 14 dispersed and mixed inside the coating liquid 10 have an average particle size D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, preferably, the average particle size D 50is in the range of 1 nm or more and less than 300 nm. The maximum particle size distribution of the nanobubbles 14 inside the coating liquid 10 is in the range of 50 nm or more and less than 500 nm, preferably in the range of 10 nm or more and less than 300 nm. The content of the nanobubbles 14 in the coating liquid 10 in which the nanobubbles 14 are dispersed and mixed is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, more preferably in the range of 50 to 90 vol.%. The total number of nanobubbles 14 per ml of the coating liquid 10 is 10 7 ~10 12 The particle size and particle size distribution of the nanobubbles 14 in the coating liquid 10, the porosity, and the total number of nanobubbles 14 were measured by nanoparticle tracking analysis (NTA). With nanoparticle tracking analysis, the particle size distribution, particle number concentration, and aggregation state of the nanobubbles 14 in the coating liquid 10 can be measured with high resolution.

[0089] In the nanoparticle tracking analysis method, the coating liquid 10 in which nanobubbles 14 are dispersed is placed in a sample chamber, and the sample chamber is irradiated with laser light. In the nanoparticle tracking analysis method, the 90° scattered light of each nanobubble 14 irradiated with laser light is detected by a highly sensitive CMOS camera. The Brownian motion of the detected particles is observed as the movement of bright spots on the camera image and tracked. The diffusion coefficient is obtained by tracking this movement, and the particle size of the nanobubbles 14 is determined by the Stokes-Einstein equation. The particle distribution (concentration) is calculated by calculating the number of nanobubbles 14 per ml from all particle counts within the camera field of view, which has a known volume, and the content of nanobubbles in the coating liquid 10 and the total number of nanobubbles 14 per ml of the coating liquid 10 are calculated. In the nanoparticle tracking analysis method, the zeta potential of the particles is determined by measuring the electrophoretic mobility when a constant voltage is applied to the cell.

[0090] The coating liquid 10 in which the nanobubbles 14 are dispersed and mixed by the nanobubble mixing device 15 is mixed with hydrogen ions H + Concentration and hydroxide ion OH -The properties of the acid-base ratio, which is approximately equal in concentration, are approximately neutral or alkaline. The nanobubbles 14 dispersed and mixed inside the coating liquid 10 are mixed into the coating liquid 10 in the form of spheres having high internal bubble pressure, and are negatively charged.

[0091] The nanobubbles 14 in the coating liquid 10 have a diameter of less than 1 μm and a Reynolds number Re of approximately 1, forming spherical bubbles. The shape (sphere) of the nanobubbles 14 was observed using an atom probe field ion microscope (APFIM). The atom probe field ion microscope is a field ion microscope (FIM) equipped with a time-of-flight mass analyzer, and individual nanobubbles 14 are observed using the field ion microscope and identified by time-of-flight mass analysis. The shape (sphere) of the nanobubbles 14 in the coating liquid 10 is reproduced with a resolution of approximately nanoscale level by displaying it three-dimensionally on a graphic workstation.

[0092] The nanobubbles 14 mixed in the coating liquid 10 rise slowly inside the coating liquid 10. The rising speed of the nanobubbles 14 depends on the liquid properties of the coating liquid 10, but in water, the nanobubbles have a diameter of about 100 μm and a Reynolds number Re of approximately 1, forming spherical bubbles. The rising speed U of a spherical bubble with a diameter d is given by the Stokes equation: U=pgd 2 / 18μ, where p is the liquid density, g is the gravitational acceleration, and μ is the liquid viscosity.

[0093] The nanobubbles 14 mixed (dissolved) inside the coating liquid 10 have a high internal bubble pressure (self-pressurizing effect). The internal bubble pressure is higher than the pressure around the bubble by ΔP according to the Young-Laplace equation: ΔP = 4σ / d due to the influence of surface tension σ. The relationship between the diameter d of the bubble in the coating liquid 10 and the internal bubble pressure is that the smaller the bubble, the higher the internal bubble pressure (3.87 "atm" for 1 μm, 29.7 "atm" for 100 nm, surface tension σ of water: 72.8 mN / m (20°C), pressure around the bubble is 1 "atm"). Therefore, when the bubble shrinks, the partial pressure of the dissolved gas component, that is, the driving force for dissolution, increases, and by reducing the gas to nano size, the gas becomes more easily dissolved in the coating liquid 10, and a large amount of nanobubbles 14 dissolves in the coating liquid 10.

[0094] The nanobubbles 14 mixed (dissolved) inside the coating liquid 10 have a large gas-liquid interface area. The gas-liquid interface area per unit volume, A / V, is expressed by the formula: A / V=6d. A / V increases as the bubble diameter d decreases, and this ratio contributes greatly to the amount of gas mixed (dissolved) in the coating liquid 10. The amount of gas mixed (dissolved) in the nanobubbles 14 is extremely large. The mass transfer rate N (mol / s) of the bubbles into the coating liquid 10 is expressed by the formula: N=K G A(pp*), where KG is the gas-phase reference overall mass transfer coefficient (mol / m 2 sPa”, A is the surface area of ​​the bubble [m 2 ], p is the partial pressure of the dissolved component in the bubble (Pa), and p* is the partial pressure of the gas phase in equilibrium with the dissolved component in the liquid phase (Pa).

[0095] When the gas in the bubbles dissolves (mixes) into the coating liquid 10, the overall mass transfer resistance is 1 / K L or 1 / K G H is the liquid phase resistance 1 / k L and gas phase resistance 1 / k G As a sum of H and Ohm's law of electrical resistance: 1 / K L =1 / K G H=1 / k L +1 / kG H. Here, K L is the liquid phase reference overall mass transfer coefficient, H is Henry's constant (p = H C ), formula: 1 / K L =1 / K G H=1 / k L +1 / k G If the gas-side mass transfer resistance 1 / kGH can be substantially ignored at H, the liquid-phase reference overall mass transfer coefficient KL and the liquid-side mass transfer coefficient kL become substantially equal.

[0096] For a spherical bubble, the Reynolds number Re<1 and the rising speed are as follows: U=pgd 2 Liquid phase mass transfer coefficient k when expressed as / 18μ L is the formula: L =D L / d[l+(1+dU / D L ) 1 / 3 ] where D L is the diffusion coefficient of the gas in the liquid phase, d is the bubble diameter, and U is the rising speed of the bubble. For example, the formula: L =D L +dl+[(1+dU / D L ) 1 / 3 ] by the bubble diameter and the liquid-side mass transfer coefficient k of the MB-water system L When the bubble diameter d is 100 μm, k L is 1.817 10 -4 "m / s", k when bubble diameter d is 10 μm L is 5.37·10 -4 "m / s", k when bubble diameter d is 1 μm L is 5.20·10 -3 The diffusion coefficient D of oxygen in the coating liquid 10 is L is 2.60 10 -9 "m 2 / s" was used.

[0097] k for the bubble diameter d L Using the value of N = K and the bubble internal pressure (atm) for the bubble diameter d, the formula is: G The mass transfer rate N was calculated using A(pp*), and rearranged. As a result, when the bubble diameter d was 10 μm, the upward velocity U was 3.26·10 -3"m / min", pressure difference ΔP is 2.91·10 4 , bubble number ratio is 1.0·10 6 , area ratio is 100, mass transfer rate ratio is 6.15·10 4 "mol / s" and 1.0·10 8 "mol / mm", and when the bubble diameter d is 100 nm, the rising speed U is 3.15·10 -7 "m / min", pressure difference ΔP is 2.91·10 6 , bubble number ratio is 1.0·10 12 , area ratio is 1.0 10 4 , mass transfer rate ratio is 5.95 10 10 "mol / s" and 1.0·10 18 "mol / mm".

[0098] If a spherical bubble with a diameter of 1 mm is divided into bubbles with a diameter of 10 μm, the number of bubbles will be 10 6 If a spherical bubble with a diameter of 1 mm is divided into bubbles with a diameter of 100 nm, the number of bubbles will increase by 10. 12 The surface area of ​​a bubble with a diameter of 1 mm is increased to 10 4 Therefore, if the mass transfer rate (dissolution rate) per unit time of a bubble with a diameter of 1 mm is 1, then the mass transfer rate (dissolution rate) of a bubble with a diameter of 10 μm is 6·10 4 The mass transfer rate (dissolution rate) per unit time for a bubble with a diameter of 1 mm is 1, and for a bubble with a diameter of 100 nm, the mass transfer rate (dissolution rate) is 6·10 10 In this way, the mass transfer rate (dissolution rate) in the coating liquid 10 increases rapidly due to the increase in the surface area and the partial pressure inside the bubbles and the decrease in the rate of rise as a result of the bubbles becoming nano-sized.

[0099] The surface potential of the nanobubbles 14 was measured using electrophoresis experimental equipment. The negatively charged nanobubbles 14 generated in the container move in a zigzag pattern by switching the electric field direction of the electrodes introduced into the electrophoresis cell (thickness 1 mm, height 23.0 mm, width 75.0 mm) every 1 second. The bubble diameter was calculated using the Stokes equation by measuring the upward speed, and the zeta potential of the bubbles was calculated using the Smoluchowski equation: ζ=μu / ε by measuring the horizontal speed. Here, ζ is the zeta potential "V", μ is the viscosity of the coating liquid 10 "kg / ms", and u is the mobility of the bubbles "m 2 / sV”, ε is the dielectric constant of the coating liquid 10 “s 2 C 2 / kgm 3 "

[0100] The nanobubbles 14 are negatively charged at -30 to -40 "mV" regardless of their particle size (bubble diameter). The cluster structure of the coating liquid 10 is formed from the molecules of the coating liquid 10 and ionized + ions and - ions, and + ions and - ions tend to fit into the structure, but - ions in particular tend to accumulate at the interface, resulting in a negative charge. The negative charge of the nanobubbles 14 causes the nanobubbles 14 in the coating liquid 10 to repel each other, and the nanobubbles 14 do not bond (unite) with each other due to electrostatic repulsion.

[0101] Since the nanobubbles 14 mixed (dissolved) in the coating liquid 10 are negatively charged, the nanobubbles 14 dispersed and mixed in the coating liquid 10 repel each other and do not bond (coalesce) with each other, which prevents the nanobubbles 14 from bonding together and becoming large bubbles, and the ultrafine nanobubbles 14 can be maintained in a dispersed state in the coating liquid 10. Since the nanobubbles 14 do not bond (coalesce) with each other in the coating liquid 10 and the ultrafine nanobubbles 14 are dispersed and mixed (dispersed and dissolved) in the coating liquid 10, the nanobubbles 14 are less likely to volatilize from the coating liquid 10, and the nanobubbles 14 can remain in the coating liquid 10 for a long period of time.

[0102] In the coating liquid 10, the nanobubbles 14 are not in a columnar state but in a spherical state having a high internal bubble pressure and are dispersed (dissolved) in a large amount at a predetermined concentration in the coating liquid 10. 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, more preferably, the average particle size D 50 A large amount of nanobubbles 14 having a size in the range of 1 nm or more and less than 300 nm are dispersed and mixed in the coating liquid 10 at a predetermined concentration (high concentration), the content of the nanobubbles 14 in the coating liquid 10 is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, and more preferably in the range of 50 to 95 vol.%, and the total number of nanobubbles 14 per ml of the coating liquid 10 is 10 7 ~10 12 Since the nanobubbles 14 are in the range of nanobubbles per 1 ml, the proportion of the coating liquid 10 itself per unit volume in the coating liquid 10 (the coating liquid 10 having the nanobubbles 14 mixed (dissolved) therein) can be reduced by the use of the ultrafine bubbles 14, and the coating amount of the coating liquid 10 itself can be reliably reduced when the coating liquid 10 (the coating liquid 10 having the nanobubbles 14 mixed (dissolved) therein) is coated on the surface 12 of the article 11 to be coated.

[0103] In the coating liquid 10, the nanobubbles 14 are not in a columnar state but in a spherical state having a high internal bubble pressure and are dispersed (dissolved) in a large amount at a predetermined concentration in the coating liquid 10. 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, more preferably, the average particle size D 50A large amount of nanobubbles 14 having a size in the range of 1 nm or more and less than 300 nm are dispersed and mixed in the coating liquid 10 at a predetermined concentration (high concentration), the content of the nanobubbles 14 in the coating liquid 10 is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, and more preferably in the range of 50 to 95 vol.%, and the total number of nanobubbles 14 per ml of the coating liquid 10 is 10 7 ~10 12 Since the nanobubbles 14 are in the range of nanobubbles per 1 ml, the proportion of the coating liquid 10 itself per unit volume in the coating liquid 10 (the coating liquid 10 having the nanobubbles 14 mixed (dissolved) therein) can be reduced by the use of the ultrafine bubbles 14, and the coating amount of the coating liquid 10 itself can be reliably reduced when the coating liquid 10 (the coating liquid 10 having the nanobubbles 14 mixed (dissolved) therein) is coated on the surface 12 of the article 11 to be coated.

[0104] The coating liquid 10 after the nanobubbles 14 are dispersed and mixed therein has a viscosity in the range of 0.98 to 1.008 mPa·s at 20°C. Furthermore, the rising speed of the nanobubbles 14 in the coating liquid 10 having the above viscosity range at 20°C after the nanobubbles 14 are dispersed and mixed therein is in the range of 0·000015 to 0.00005 mm / min. The nanobubbles 14 have an extremely small volume, so that their rising speed in the coating liquid 10 is extremely slow. If the rising speed of the nanobubbles 14 in the coating liquid 10 exceeds 0.00005 mm / min, it is difficult to keep the nanobubbles 14 in the coating liquid 10 for a long period of time, and the nanobubbles 14 may volatilize from the coating liquid 10 within the target residence time.

[0105] The forces acting on the nanobubbles 14 inside the coating liquid 10 include buoyancy and drag. Buoyancy is proportional to the volume of the nanobubbles 14 (proportional to the cube of the radius of the nanobubbles 14). Drag is proportional to the cross-sectional area of ​​the nanobubbles 14 (proportional to the square of the radius of the nanobubbles 14) and proportional to the square of the rising speed of the nanobubbles 14. Specifically, if the radius of the nanobubbles 14 is r, the density of the coating liquid 10 is ρ, the gravitational acceleration is g, the viscosity of the coating liquid 10 is η, and the moving speed of the nanobubbles 14 is u, then the buoyancy acting on the nanobubbles 14 (ignoring the density of the nanobubbles) is expressed by Archimedes' principle as follows: F=4πr 3 It is expressed by ρg / 3.

[0106] The resistance force acting on the nanobubbles 14 is expressed by the formula (2): F = 6πηru according to Stokes' theorem. From the formulas (1) and (2), the moving speed u of the nanobubbles 14 inside the coating liquid 10 is expressed by the formula (3): u = (2 / 9)r 2 It is expressed by ρg / η. The rising speed of the nanobubbles 14 in the coating liquid 10 was calculated from formula (3). As is clear from formula (3), the larger the radius r (particle size) of the nanobubbles 14, the higher the moving speed u of the nanobubbles 14 in the coating liquid 10.

[0107] When the radius r of the nanobubble 14 under 1 atmospheric pressure is a, the radius r and the water depth h are calculated by the following formula (4): r = a × {101325 / (ρgh + 101325)} 1 / 3 As is clear from formulas (3) and (4), the nanobubbles 14 have larger particle sizes and rise faster as the water depth of the coating liquid 10 becomes shallower.

[0108] As a hypothesis, nanobubbles 14 with a diameter of less than 1.0 μm have their solubility reduced by the salting-out phenomenon, and remain stable for a long period of time inside the coating liquid 10. If nanobubbles 14 continue to exist stably for a long period of time due to the salting-out phenomenon, there would be no coating liquid 10 containing nanobubbles 14 with a pH close to 7, but there are cases in which stable nanobubbles 14 exist even in neutral liquids.

[0109] Generally, when nanobubbles 14 are mixed with larger microbubbles, the nanobubbles 14 rise to the surface due to the influence of the latter larger microbubbles, or are affected by cavitation destruction due to external pressure, shortening the lifespan of the nanobubbles 14. However, when nanobubbles 14 are generated in the nanobubble mixing device 15, large microbubbles with diameters of 1.0 μm or more are not generated, so the lifespan of the generated nanobubbles 14 can be made longer.

[0110] (Item 11 (substrate) to be coated) The article 11 to be coated with the coating liquid 10 is a metal molded product, a plastic molded product, a glass molded product, a rubber molded product, a leather molded product, a wood molded product, a paper molded product, a woven fabric molded product, or a nonwoven fabric molded product. The shapes of these molded products are arbitrary (free). Materials for metal molded products include iron, aluminum, duralumin, stainless steel, copper, gold, silver, titanium, nickel, alloys, etc. Metal molded products made of these materials have various shapes such as plates, rods, and other three-dimensional shapes. Materials for plastic molded products include known thermoplastic resins such as polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyamide (nylon), vinyl chloride resin, acrylic resin, silicone resin, fluororesin, polyimide resin, and polysulfone resin, and thermosetting resins such as epoxy resin, melamine resin, phenolic resin, and unsaturated polyester resin. Plastic molded products made of these materials have various shapes such as films, sheets, plates, and other three-dimensional shapes.

[0111] (Method of Coating (Applying) Coating Liquid 10) The coating liquid 10 is coated or sprayed on the surface 12 of the article 11 to be coated, and reacts with water to form (form) a single-layer or multi-layer ultra-thin inorganic coating film 13. The inorganic coating film 13 is formed as a coating having a thickness in the range of 5 nm to 1 μm, preferably 50 nm to 500 nm. There is no particular limitation on the method of coating the surface 12 of the article 11 with the coating liquid 10, and the surface 12 is coated by a coating method suitable for the shape of the article 11 to be coated. For example, the surface 12 is coated by a spray method, a dipping method, a brush coating method, a roll coating method, a gravure coating method, a flexography method, an inkjet method, or the like. There is no particular limitation on the amount of coating (amount of application) of the coating liquid 10, and the amount of coating is determined according to the surface performance required for the article 11 to be coated. Generally, the amount of coating is 0.1 to 20 g / m in terms of solid content. 2 The coating amount is 0.1g / m 2 If the coating amount is less than 20 g / m2, the inorganic coating film 13 having the desired properties cannot be formed. 2 If it exceeds this value, the thickness of the inorganic coating film 13 increases more than necessary, and the inorganic coating film 13 loses its flexibility.

[0112] In addition, as a pretreatment step prior to the coating step of the coating liquid 10, water such as purified water (H 2 O) may be sprayed onto the surface 12 of the article 11 to adhere the water to the surface 12 of the article 11. In this manner, a chemical reaction between the water adhered to the surface 12 of the article 11 and the components contained in the coating liquid 10 is promoted, and the inorganic coating film 13 can be rapidly formed on the surface 12 of the article 11, and a strong inorganic coating film 13 can be formed on the surface 12 of the article 11.

[0113] Furthermore, a coating liquid containing inorganic polysilazane as a main component can be coated as a primer on the surface 12 of the article 11 as a pretreatment step prior to the coating step of the coating liquid 10. For example, when a solution of inorganic polysilazane (1 wt % solution) is coated and then the coating liquid 10 is coated, the rust prevention (durability) of the inorganic coating film 13 is improved compared to when only the coating liquid 10 is simply coated.

[0114] (Mechanism of formation of inorganic coating film 13) Next, a mechanism for forming the inorganic coating film 13 on the surface 12 of the article 11 will be described. After the surface 12 of the article 11 is coated with the coating liquid 10 in the coating process, the surface 12 of the article 11 is heated to a temperature of 400° C. or higher while irradiating the surface 12 of the article 11 with ultraviolet rays.

[0115] As shown in FIG. 2(a), a small amount of moisture (water droplets) is attached to the surface 12 of the article 11 due to condensation or humidity in the air (water (H 2 When the surface 12 of the article 11 is coated with the coating liquid 10 in a thin film form by a coating process, the -(SiR 1 R 2 -NR 3 )-unit components and / or -(SiR 1 R 2 -NR 3 )-unit component is moisture in the air (H 2 0), an organic composite structure (-(Si(CH in the example of the structural image of the inorganic coating film 13 shown in FIG. 3) in which an organic functional group is bonded as a side chain to a part of the main chain by a siloxane bond (Si-O-Si) is formed on the surface 12 of the article 11. 3 ) 2 -O-Si(CH 3 ) 2The inorganic coating film 13 (glass coating layer (amorphous glass coating)) having a crystalline (crystalline)-unit is generated. The inorganic coating film 13 is vitrified (inorganized) at approximately 100%. Also, a small amount of gas (NH 3 ,H 2 These gases do not remain on the surface 12 of the article 11 but evaporate (emit) into the atmosphere.

[0116] As shown in FIG. 2(b), the coating liquid 10 containing polysilazane and / or siloxane undergoes a chemical reaction (deammoniation cross-linking) with moisture contained in the air in the surface layer 28 in contact with the air, whereby gases such as hydrogen and ammonia, which are by-products of the inorganic coating film 13, volatilize from the surface 12 to the outside air, and a coating layer 29 is formed (generated) on the surface 12 side of the inorganic coating film 13.

[0117] The coating liquid 10 coated on the surface 12 of the article 11 undergoes a chemical reaction (deammonia cross-linking) with moisture (water droplets) attached to the surface 12 or with hydroxyl groups -OH (see Figure 3) present as terminal ends on the surface 12 in the back layer 30 in contact with the surface 12 of the article 11, whereby gases such as hydrogen and ammonia rise within the coating layer and volatilize from the surface 12 to the outside air, and a coating layer 31 on the back side of the inorganic coating film 13 is formed (generated).

[0118] First, the glass coating layers 11, 12 are generated on the surface layer 28 and the back layer 30 of the coating liquid 10. Next, the coating layers 29, 31 (glass coating layers) are formed and expanded from the surface layer 28 side toward the back layer 30 side, and the coating layers 29, 31 (glass coating layers) expand from the back layer 30 side toward the surface layer 28 side, so that the coating layer 29 (glass coating layer) of the intermediate layer 33 is formed (generated) in sequence, and finally, the inorganic coating film 13 is formed (generated) on the surface layer 28 in contact with the outside air, the back layer 30 in contact with the surface 12 of the article 11, and the intermediate layer 33 between the surface layer 28 and the back layer 30.

[0119] The inorganic coating film 13 made of polysilazane and / or siloxane is a glass coating layer that is approximately 100%. The inorganic coating film 13 is mainly composed of SiO2 generated by reacting polysilazane and / or siloxane, and thus a glass coating layer that spreads easily in a plane and has high density and high hardness (vertical hardness of about 6H to 9H) is formed, forming an ultra-thin film structure at the nano level.

[0120] The inorganic coating film 13 is formed as an ultra-thin film at the nano-level because the coating liquid 10 contains polysilazane and / or siloxane. The film thickness is in the range of 5 nm to 1 μm, and preferably in the range of 50 nm to 500 nm. Although the inorganic coating film 13 is a coating film mainly composed of SiO2, it has excellent flexibility, and in combination with the anchor effect of the anchor parts 36, it will not peel off even if the surface 12 of the article 11 is a material that causes deformation such as a cloth material, and the coating state of the inorganic coating film 13 can be maintained by following the deformation of the surface 12 of the article 11.

[0121] As shown in FIG. 4, the inorganic coating film 13 formed by hardening the coating liquid 10 on the surface 12 of the article 11 has particles with an average particle diameter D 90 However, nanobubbles 14 smaller than 1 μm remain as they are and are trapped in the inorganic coating film 13, and the nanobubbles 14 are dispersed (dissolved) at a predetermined concentration. The nanobubbles 14 dispersed and mixed inside the inorganic coating film 13 are spheres with high internal bubble pressure, similar to the state in which they were dispersed and mixed in the coating liquid 10, and the average particle diameter D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm to 500 nm, more preferably, the average particle size D 50is in the range of 1 nm or more and less than 300 nm. The maximum particle size distribution of the nanobubbles 14 inside the inorganic coating film 13 is in the range of 50 nm to 500 nm, preferably in the range of 10 nm to 300 nm. The content of the nanobubbles 14 in the inorganic coating film 13 is in the range of 10 to 95 vol.%, preferably in the range of 30 to 95 vol.%, more preferably in the range of 50 to 95 vol.%. 2 The total number of nano bubbles per 14 is 10 7 ~10 12 It is in the range of pieces.

[0122] The nanobubbles 14 mixed (dissolved) inside the coating liquid 10 coated to a predetermined film thickness (5 nm to 1 μm, preferably 50 nm to 500 nm) have a particle size that gradually increases from the back layer 30 (bottom) to the surface layer 28 (top) of the coating liquid 10 within the above range. Therefore, the nanobubbles 14 located in the back layer 30 (bottom) of the coating liquid 10 have the smallest particle size, the nanobubbles 14 located in the surface layer 28 (top) of the coating liquid 10 have the largest particle size, and the nanobubbles 14 located in the intermediate layer 33 (middle part) of the coating liquid 10 have a particle size intermediate between those of the nanobubbles 14 located in the back layer 30 (bottom) and the surface layer 28 (top).

[0123] As shown in an example of the structure image of the inorganic coating film 13 in FIG. 3, the alkyl silicate condensate is chemically reacted with water to generate -(Si(OH) 2 -O-Si(OH) 2 It is assumed that a crosslinking reaction occurs between the hydrolysis product having a siloxane bond (Si-O-Si) and a part of the main chain in each coating layer (surface layer 28, intermediate layer 33, back layer 30) and a crosslinked structure 34 is formed, so that the inorganic coating film 13 has a dense and flexible structure. In addition, the formation of the crosslinked structure 34 allows hydrophobic methyl groups (CH 3) and a hydrophilic hydroxyl group (OH) derived from the hydrolysis product of the alkylsilicate condensation product.

[0124] 2(c), the surface 12 of the article 11 before being coated with the inorganic coating film 13 has many microscopic irregularities 35 formed due to small scratches and the like caused during the manufacturing process, etc., unless a special surface treatment such as mirror finishing is performed. When the coating liquid 10 is coated onto the surface 12 of the article 11 and hardens while penetrating into the irregularities 35, the anchor parts 36 of the inorganic coating film 13 that have hardened and penetrated into the irregularities 35 exert an anchor effect, and the inorganic coating film 13 adheres more firmly to the surface 12 of the article 11.

[0125] When the surface 12 of the article 11 is a smooth surface with almost no unevenness 35, the surface 12 of the article 11 may be roughened as a pretreatment for coating with the coating liquid 10 to form unevenness 35 with an average roughness of about 1 to 500 μm on the surface 12 of the article 11. By performing the roughening treatment in this manner, an anchor effect can be obtained by the anchor portions 36 of the inorganic coating film 13. After the roughening treatment, a cleaning treatment is performed in which metal powder, plastic powder, etc. generated on the surface 12 of the article 11 is blown away using an air injection means such as an air gun. After the cleaning treatment, condensation, etc. is generated on the surface 12 of the article 11 by leaving it for a predetermined time, and naturally occurring moisture is attached to the surface 12.

[0126] In this case, after the surface 12 of the article 11 is roughened and cleaned, moisture is actively applied to the surface 12 of the article 11 on which the uneven portion 35 has been formed by roughening using a moisture applying means such as a sprayer, and then the surface 12 is coated with the coating liquid 10. In this manner, a chemical reaction between the moisture applied to the surface 12 of the article 11 and the coating liquid 10 in contact with the surface 12 of the article 11 can be promoted. Note that moisture may be applied to the surface 12 of the article 11 by a moisture applying means without performing a roughening treatment on the surface 12 of the article 11.

[0127] (Shape of the coating layer formed by the inorganic coating film 13) The nanobubbles 14 present (dissolved) inside the inorganic coating film 13 formed to a predetermined film thickness (5 nm to 1 μm, preferably 50 nm to 500 nm) have a particle size that gradually increases from the back layer 30 (bottom) to the surface layer 28 (top) of the inorganic coating film 13 within the above range. Therefore, the nanobubbles 14 located in the back layer 30 (bottom) of the inorganic coating film 13 have the smallest particle size, the nanobubbles 14 located in the surface layer 28 (top) of the inorganic coating film 13 have the largest particle size, and the nanobubbles 14 located in the intermediate layer 33 (middle part) of the inorganic coating film 13 have a particle size intermediate between those of the nanobubbles 14 located at the bottom and the top.

[0128] The uneven portion 35 initially formed on the surface 12 of the article 11 before being coated with the inorganic coating film 13 made of polysilazane and / or siloxane is covered by the inorganic coating film 13, so that the surface 12 of the article 11 becomes smoother after being coated with the inorganic coating film 13 than before being coated with the inorganic coating film 13.

[0129] Fig. 6 is a diagram showing the blending ratio, porosity, total number of nanobubbles, and nanobubble diameter of the coating liquid 10 of Samples A to E and the inorganic coating film 13 made from the coating liquid 10 of Samples A to E, and Fig. 7 is a diagram showing the blending ratio, porosity, total number of nanobubbles, and nanobubble diameter of the coating liquid 10 of Samples F to H and the inorganic coating film 13 made from the coating liquid 10 of Samples F to H. Fig. 8 is a diagram showing evaluations of the flexibility, impact resistance, and corrosion resistance of the inorganic coating film 13 made from the coating liquid 10 of Samples A to E, and Fig. 9 is a diagram showing evaluations of the flexibility, impact resistance, and corrosion resistance of the inorganic coating film 13 made from the coating liquid 10 of Samples F to H.

[0130] Samples A to E were prepared in which the blending ratio of the organosilicon material (polysilazane and / or siloxane) was in the range of 30 to 60 wt%, the blending ratio of the alkylsilicate condensate was in the range of 10 to 15 wt%, and the blending ratio of the inert organic solvent was in the range of 30 to 60 wt% relative to the total mass of the coating liquid 10. Furthermore, Samples F to H were prepared in which the blending ratio of the organosilicon material (polysilazane and / or siloxane) was in the range of 5 to 25 wt%, the blending ratio of the alkylsilicate condensate was in the range of 10 to 15 wt%, and the blending ratio of the inert organic solvent was in the range of 60 to 80 wt% relative to the total mass of the coating liquid 10.

[0131] The coating liquid 10 of Samples A to H is composed of the same raw materials selected from the above-mentioned polysilazane and / or siloxane, alkyl silicate condensate, and inert organic solvent, and the content ratio of the raw materials is adjusted for each sample, and spherical nanobubbles 14 are dispersed and mixed (dispersed and dissolved) inside the coating liquid 10.

[0132] Using the coating method described above, the coating liquid 10 of Samples A to H was uniformly coated without unevenness to approximately the same thickness (5 nm to 1 μm, preferably 50 nm to 500 nm) on the surface 12 of the article 11 (aluminum foil and steel plate (metal molded product)) to be coated, and then the surface 12 of the article 11 was irradiated with ultraviolet light while heating to 400°C or higher with infrared light to dry and harden it, thereby covering the surface 12 of the article 11 with an inorganic coating film 13 (approximately 100% glass coating layer) with a film thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm, made from the coating liquid 10 of Samples A to H.

[0133] Spherical nanobubbles 14 are dispersed (dispersed and dissolved) inside the inorganic coating film 13 formed on the surface 12 of the article 11 from the coating liquid 10 of Samples A to H. Since the viscosity of the coating liquid 10 increases as the blending ratio (content) of polysilazane and / or siloxane increases, the coating liquid 10 of Samples C to D, which has a high blending ratio (content) of polysilazane and / or siloxane, may be applied in a single layer, while the coating liquid 10 of Samples A and B, which has a low blending ratio (content) of polysilazane and / or siloxane, may be applied in multiple layers, so that the surface 12 of the aluminum foil and steel plate (metal molded product) may be coated with approximately the same film thickness.

[0134] FIG. 6 shows the blending ratio of the organosilicon material (polysilazane and / or siloxane), the alkyl silicate condensate, and the inert organic solvent in the coating liquid 10 of Samples A to E, the porosity of the coating liquid 10, the total number of nanobubbles 14 mixed (dissolved) in the coating liquid 10, and the particle size of the nanobubbles 14 mixed (dissolved) in the coating liquid 10, as well as the blending ratio of the organosilicon material (polysilazane and / or siloxane), the alkyl silicate condensate, and the inert organic solvent in the inorganic coating film 13 formed from the coating liquid 10 of Samples A to E, the porosity of the inorganic coating film 13, the total number of nanobubbles 14 mixed (dissolved) in the inorganic coating film 13, and the particle size of the nanobubbles 14 mixed (dissolved) in the inorganic coating film 13.

[0135] 7 shows the blending ratio of the organosilicon material (polysilazane and / or siloxane), alkyl silicate condensate, and inert organic solvent in the coating liquid 10 of Samples F to H, the porosity of the coating liquid 10, the total number of nanobubbles 14 mixed (dissolved) in the coating liquid 10, and the particle size of the nanobubbles 14 mixed (dissolved) in the coating liquid 10, as well as the blending ratio of the organosilicon material (polysilazane and / or siloxane), alkyl silicate condensate, and inert organic solvent in the inorganic coating film 13 made from the coating liquid 10 of Samples F to H, the porosity of the inorganic coating film 13, the total number of nanobubbles 14 mixed (dissolved) in the inorganic coating film 13, and the particle size of the nanobubbles 14 mixed (dissolved) in the inorganic coating film 13. Samples A to H were evaluated for flexibility, impact resistance, and corrosion resistance.

[0136] (Method for evaluating flexibility of inorganic coating film 13) In order to evaluate the flexibility of the inorganic coating film 13 made from the coating liquid 10 of Samples A to H, a curved surface with a radius of curvature R of about 5 mm to 10 mm was formed on the thin aluminum foil having the surface 12 covered with the inorganic coating film 13, and the state of the shape change occurring in the inorganic coating film 13 was visually confirmed and evaluated according to the following criteria: ◯: no cracks, △: slight cracks, ×: many cracks.

[0137] (Method of Evaluating Impact Resistance of Inorganic Coating Film 13) As a method for evaluating the impact resistance of the inorganic coating film 13 made from the coating liquid 10 of Samples A to H, an impact was applied under the same conditions to a steel plate having a surface 12 covered with the inorganic coating film 13 using a DuPont impact tester, and the state of shape change caused in the inorganic coating film 13 was visually confirmed and evaluated according to the following criteria: ◯: no cracks, △: slight cracks, ×: many cracks.

[0138] (Method of evaluating corrosion resistance of inorganic coating film 13) In order to evaluate the corrosion resistance of the inorganic coating film 13 made from the coating liquid 10 of Samples A to H, the steel plate having the surface 12 covered with the inorganic coating film 13 was placed for two months in the same environment as that in which it is exposed to flying foreign matter (in a harsh environment near a coke oven in a steelworks, exposed to coke oven gas), and the state of rust or discoloration on the surface was visually confirmed and evaluated according to the following criteria. ◯ means no rust or discoloration, and × means rust or discoloration.

[0139] The coating liquid 10 of sample A shown in FIG. 6 and the inorganic coating film 13 made from the coating liquid 10 have a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (inorganic coating film 13) of 30 wt %, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (inorganic coating film 13) of 15 wt %, a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (inorganic coating film 13) of 55 wt %, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 50 vol. %, and a density of nanobubbles 14 per ml of the coating liquid 10 (1 mm of the inorganic coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 11 pieces / 1ml(10 7 ~10 11 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed (dispersed and mixed) inside the coating liquid 10 (inorganic coating film 13) in a spherical (spherical) state have a particle size of 1 nm to 500 nm.

[0140] Spherical (globular) nanobubbles 14 with diameters of 1 nm to 500 nm are evenly dispersed and mixed (dispersed and dissolved) inside the coating liquid 10 of sample A. Since the nanobubbles 14 mixed in the coating liquid 10 of sample A are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles. Furthermore, inside the inorganic coating film 13 created by hardening the coating liquid 10 of sample A, spherical (globular) nanobubbles 14 with diameters of 1 nm to 500 nm are evenly dispersed and mixed (dispersed and dissolved) (trapped) inside.

[0141] An inorganic coating film 13 on a surface 12 of an article 11 (aluminum foil and steel plate (metal molded product)) made by coating with a coating liquid 10 of sample A containing dispersed and mixed spherical (spherical) nanobubbles 14 with a particle size of 1 nm to 500 nm has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 10). It was found that by using the coating liquid 10 of sample A, an inorganic coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.

[0142] The coating liquid 10 prepared as sample B and the inorganic coating film 13 made from the coating liquid 10 had a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (inorganic coating film 13) of 40 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (inorganic coating film 13) of 15 wt%, and a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (inorganic coating film 13) of 45 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 60 vol.%, and a per ml of the coating liquid 10 (1 mm of the inorganic coating film 13), 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 11 pieces / 1ml(10 7 ~1011 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed (dispersed and mixed) inside the coating liquid 10 (inorganic coating film 13) in a spherical (spherical) state have a particle size of 1 nm to 600 nm.

[0143] Spherical (globular) nanobubbles 14 with diameters of 1 nm to 600 nm are evenly dispersed and mixed (dispersed and dissolved) throughout the coating liquid 10 of sample B. Since the nanobubbles 14 mixed in the coating liquid 10 of sample B are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles. Furthermore, spherical (globular) nanobubbles 14 with diameters of 1 nm to 600 nm are evenly dispersed and mixed (dispersed and dissolved) throughout (trapped) within the inorganic coating film 13 formed by hardening the coating liquid 10 of sample B.

[0144] An inorganic coating film 13 on a surface 12 of an article 11 (aluminum foil and steel plate (metal molded product)) made by coating with a coating liquid 10 of sample B containing dispersed and mixed spherical (spherical) nanobubbles 14 with a particle size of 1 nm to 600 nm has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 10). It was found that by using the coating liquid 10 of sample B, an inorganic coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.

[0145] The coating liquid 10 prepared as sample C and the inorganic coating film 13 made from the coating liquid 10 had a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (inorganic coating film 13) of 50 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (inorganic coating film 13) of 13 wt%, and a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (inorganic coating film 13) of 37 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 70 vol.%, and a per ml of the coating liquid 10 (1 mm of the inorganic coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 12 pieces / 1ml(10 7 ~10 12 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed (dispersed and mixed) inside the coating liquid 10 (inorganic coating film 13) in a spherical (spherical) state have a particle size of 50 nm to 700 nm.

[0146] Spherical (globular) nanobubbles 14 with diameters of 50 nm to 700 nm are evenly dispersed and mixed (dispersed and dissolved) throughout the coating liquid 10 of sample C. Since the nanobubbles 14 mixed in the coating liquid 10 of sample C are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles. Furthermore, spherical (globular) nanobubbles 14 with diameters of 50 nm to 700 nm are evenly dispersed and mixed (dispersed and dissolved) throughout (trapped) within the inorganic coating film 13 formed by hardening the coating liquid 10 of sample C.

[0147] The inorganic coating film 13 on the surface 12 of an article 11 (aluminum foil and steel plate (metal molded product)) made by coating with the coating liquid 10 of sample C, in which spherical (globular) nanobubbles 14 with a particle size of 50 nm to 700 nm are dispersed and mixed, has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 10). It was found that by using the coating liquid 10 of sample C, an inorganic coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.

[0148] The coating liquid 10 prepared as sample D and the inorganic coating film 13 made from the coating liquid 10 had a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (inorganic coating film 13) of 55 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (inorganic coating film 13) of 10 wt%, and a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (inorganic coating film 13) of 35 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 80 vol.%, and a per ml of the coating liquid 10 (1 mm of the inorganic coating film 13), 2 The total number of nanobubbles per 8 ~10 12 pieces / 1ml(10 8 ~10 12 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed inside the coating liquid 10 (inorganic coating film 13) in a spherical (spherical) state have a particle size of 100 nm to 800 nm.

[0149] Inside the coating liquid 10 of sample D, spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed in the coating liquid 10 of sample D are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles in diameter. Furthermore, inside the inorganic coating film 13 created by hardening the coating liquid 10 of sample D, spherical (spherical) nanobubbles 14 with diameters of 100 nm to 800 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout (trapped).

[0150] The inorganic coating film 13 on the surface 12 of an article 11 (aluminum foil and steel plate (metal molded product)) made by coating with the coating liquid 10 of sample D, in which spherical (globular) nanobubbles 14 with particle sizes of 100 nm to 800 nm are dispersed, has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 10). It was found that by using the coating liquid 10 of sample D, an inorganic coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.

[0151] The coating liquid 10 prepared as sample E and the inorganic coating film 13 made from the coating liquid 10 had a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (coating film 13) of 60 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (inorganic coating film 13) of 10 wt%, and a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (inorganic coating film 13) of 30 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 95 vol.%, and a per ml of the coating liquid 10 (1 mm of the inorganic coating film 13), 2 The total number of nano bubbles (14 per bubble) is 10 8 ~10 12 pieces / 1ml(10 8~10 12 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed inside the inorganic coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 900 nm.

[0152] Inside the coating liquid 10 of sample E, spherical (spherical) nanobubbles 14 with diameters of 100 nm to 900 nm are uniformly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed (dissolved) in the coating liquid 10 of sample E are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles in diameter. Furthermore, inside the inorganic coating film 13 formed by hardening the coating liquid 10 of sample E, spherical (spherical) nanobubbles 14 with diameters of 100 nm to 900 nm are uniformly dissolved and mixed (dispersed and dissolved) throughout (trapped).

[0153] An inorganic coating film 13 on a surface 12 of an article 11 (aluminum foil and steel plate (metal molded product)) made by coating with the coating liquid 10 of sample E, in which spherical (globular) nanobubbles 14 with a particle size of 100 nm to 900 nm are dispersed and mixed, has high flexibility, impact resistance, and corrosion resistance, and is rated as good for flexibility, impact resistance, and corrosion resistance (see FIG. 10). It was found that by using the coating liquid 10 of sample E, an inorganic coating film 13 having excellent flexibility, impact resistance, and corrosion resistance can be made, even though it is an ultra-thin film with a thickness of 5 nm to 1 μm, preferably 50 nm to 500 nm.

[0154] By dispersing (dispersing and dissolving) a large number of fine spherical (spherical) nanobubbles 14 in the coating liquid 10 of Samples A to E, the proportion of the coating liquid 10 itself per unit volume of the coating liquid 10 is reduced, and the coating amount of the coating liquid 10 itself is reduced when the coating liquid 10 of Samples A to E is coated on the surface 12 of the article 11 to be coated. Furthermore, by dispersing and mixing the nanobubbles 14 in the inorganic coating film 13 made from the coating liquid 10 of Samples A to E in which a large number of fine nanobubbles 14 are dispersed, the proportion of the inorganic coating film 13 itself per unit area of ​​the inorganic coating film 13 is reduced, and the coating amount of the inorganic coating film 13 itself is reduced when the surface 12 of the article 11 to be coated is coated.

[0155] In addition to the flexibility of the inorganic coating film 13 being improved by the numerous tiny nanobubbles 14 dispersed and mixed in the inorganic coating film 13 made from the coating liquid 10 of Samples A to E, the gas mixed in the inorganic coating film 13 is nano-sized, so it does not affect its impact resistance or corrosion resistance.It was found that the inorganic coating films 13 made from the coating liquid 10 of Samples A to E are ultra-thin films, yet have high impact resistance and high corrosion resistance, and are extremely unlikely to peel off or crack.

[0156] The coating liquid 10 prepared as sample F and the inorganic coating film 13 made from the coating liquid 10 had a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (inorganic coating film 13) of 25 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (inorganic coating film 13) of 10 wt%, a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (inorganic coating film 13) of 65 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 30 vol.%, and a per ml of the coating liquid 10 (1 mm of the inorganic coating film 13). 2The total number of nano bubbles (14 per bubble) is 10 6 ~10 8 pieces / 1ml(10 6 ~10 8 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed inside the inorganic coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 900 nm.

[0157] The coating liquid 10 of sample F has spherical nanobubbles 14 with diameters of 100 nm to 900 nm evenly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed in the coating liquid 10 of sample F are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles. Furthermore, the inorganic coating film 13 formed by hardening the coating liquid 10 of sample F has spherical nanobubbles 14 with diameters of 100 nm to 900 nm evenly dispersed and mixed (dispersed and dissolved) throughout (trapped).

[0158] By dispersing (dispersing and dissolving) a large number of fine spherical (spherical) nanobubbles 14 in the coating liquid 10 of sample F, the proportion of the coating liquid 10 itself per unit volume of the coating liquid 10 is reduced, and the coating amount of the coating liquid 10 itself is reduced when the coating liquid 10 of sample F is coated on the surface 12 of the article 11 to be coated. In addition, by dispersing and mixing the nanobubbles 14 in the inorganic coating film 13 made from the coating liquid 10 of sample F in which a large number of fine nanobubbles 14 are dispersed, the proportion of the inorganic coating film 13 itself per unit area of ​​the inorganic coating film 13 is reduced, and the coating amount of the inorganic coating film 13 itself is reduced when the surface 12 of the article 11 to be coated is coated.

[0159] The coating liquid 10 prepared as sample G and the inorganic coating film 13 made from the coating liquid 10 had a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (inorganic coating film 13) of 10 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (inorganic coating film 13) of 15 wt%, and a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (inorganic coating film 13) of 75 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 40 vol.%, and a per ml of the coating liquid 10 (1 mm of the inorganic coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 6 ~10 9 pieces / 1ml(10 6 ~10 9 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed inside the inorganic coating film 13 in a spherical (spherical) state have a particle size of 100 nm to 800 nm.

[0160] The coating liquid 10 of sample G has spherical nanobubbles 14 with diameters of 100 nm to 800 nm evenly dispersed and mixed (dispersed and dissolved) throughout. Since the nanobubbles 14 mixed in the coating liquid 10 of sample G are negatively charged, the nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles. Furthermore, the inorganic coating film 13 formed by hardening the coating liquid 10 of sample G has spherical nanobubbles 14 with diameters of 100 nm to 800 nm evenly dispersed and mixed (dispersed and dissolved) throughout (trapped).

[0161] By dispersing (dispersing and dissolving) a large number of fine spherical (spherical) nanobubbles 14 in the coating liquid 10 of sample G, the proportion of the coating liquid 10 itself per unit volume of the coating liquid 10 is reduced, and the coating amount of the coating liquid 10 itself is reduced when the coating liquid 10 of sample G is coated on the surface 12 of the article 11 to be coated. Furthermore, by dispersing and mixing the nanobubbles 14 in the inorganic coating film 13 made from the coating liquid 10 of sample G in which a large number of fine nanobubbles 14 are dispersed, the proportion of the inorganic coating film 13 itself per unit area of ​​the inorganic coating film 13 is reduced, and the coating amount of the inorganic coating film 13 itself is reduced when the surface 12 of the article 11 to be coated is coated.

[0162] The coating liquid 10 prepared as sample H and the inorganic coating film 13 made from the coating liquid 10 had a mixing ratio of the organosilicon material (polysilazane and / or siloxane) to the total mass of the coating liquid 10 (inorganic coating film 13) of 5 wt%, a mixing ratio of the alkyl silicate condensate to the total mass of the coating liquid 10 (inorganic coating film 13) of 15 wt%, a mixing ratio of the inert organic solvent to the total mass of the coating liquid 10 (inorganic coating film 13) of 80 wt%, a content of nanobubbles 14 in the coating liquid 10 (inorganic coating film 13) of 45 vol.%, and a per ml of the coating liquid 10 (1 mm of the inorganic coating film 13). 2 The total number of nano bubbles (14 per bubble) is 10 7 ~10 10 pieces / 1ml(10 7 ~10 10 pieces / 1mm 2 ), the nanobubbles 14 dispersed and mixed inside the inorganic coating film 13 in a spherical (spherical) state have a particle size of 50 nm to 700 nm.

[0163] The coating liquid 10 of sample H has spherical nanobubbles 14 with diameters of 50 nm to 700 nm dispersed and mixed (dispersed and dissolved) evenly throughout. The nanobubbles 14 mixed (dissolved) in the coating liquid 10 of sample H are negatively charged, so the nanobubbles 14 do not bond (coalesce) with each other, and the nanobubbles 14 do not become large bubbles. Furthermore, the inorganic coating film 13 formed by hardening the coating liquid 10 of sample H has spherical nanobubbles 14 with diameters of 50 nm to 700 nm dispersed and mixed (dispersed and dissolved) evenly throughout (trapped).

[0164] By dispersing (dispersing and dissolving) a large number of fine spherical (spherical) nanobubbles 14 in the coating liquid 10 of Samples F to H, the proportion of the coating liquid 10 itself per unit volume of the coating liquid 10 is reduced, and the coating amount of the coating liquid 10 itself is reduced when the coating liquid 10 of Samples F to H is coated on the surface 12 of the article 11 to be coated. In addition, by dispersing and mixing the nanobubbles 14 in the inorganic coating film 13 made from the coating liquid 10 of Samples F to H in which a large number of fine nanobubbles 14 are dispersed, the proportion of the inorganic coating film 13 itself per unit area of ​​the inorganic coating film 13 is reduced, and the coating amount of the inorganic coating film 13 itself is reduced when the surface 12 of the article 11 to be coated is coated.

[0165] However, the inorganic coating film 13 on the surface 12 (aluminum foil and steel plate (metal molded product)) of the article 11 made by coating with the coating liquid 10 of sample F has high corrosion resistance and is rated as ◯ for corrosion resistance, but is poor in flexibility and impact resistance because the blending ratio of the organosilicon material (organic polysilazane and / or siloxane) is insufficient, and is rated as △ for flexibility and impact resistance (see FIG. 11). It was found that it is difficult to make an inorganic coating film 13 that is excellent in all of flexibility, impact resistance, and corrosion resistance, even if the coating liquid 10 with the blending ratio of sample F is used.

[0166] In addition, the inorganic coating film 13 on the surface 12 of the article 11 (aluminum foil and steel plate (metal molded product)) made by coating with the coating liquid 10 of sample G is inferior in flexibility due to the low blending ratio of the organosilicon material (organic polysilazane and / or siloxane), and the flexibility is evaluated as △, and the impact resistance and corrosion resistance are not recognized, and the impact resistance and corrosion resistance are evaluated as × (see FIG. 11). It was found that even if the coating liquid 10 with the blending ratio of sample G is used, it is not possible to make an inorganic coating film 13 with excellent flexibility, impact resistance, and corrosion resistance.

[0167] Furthermore, the inorganic coating film 13 on the surface 12 of the article 11 (aluminum foil and steel plate (metal molded product)) made by coating with the coating liquid 10 of sample H was affected by the low blending ratio of the organosilicon material (organic polysilazane and / or siloxane), and its flexibility, impact resistance, and corrosion resistance were not recognized, and the evaluations of flexibility, impact resistance, and corrosion resistance were poor (see FIG. 11). It was found that even if the coating liquid 10 with the blending ratio of sample H was used, it was not possible to make an inorganic coating film 13 with excellent flexibility, impact resistance, and corrosion resistance.

[0168] The inorganic coating film 13 made from the coating solution 10 of samples A to E has independent ultrafine particles (average particle size D 90 is less than 1 μm, preferably the average particle size D 50 is in the range of 1 nm or more and less than 500 nm, preferably, the average particle size D 50Since a large number of spherical nanobubbles 14 (spherical spaces) having a size in the range of 1 nm or more and less than 300 nm are dispersed and mixed (dispersed and dissolved) in the inorganic coating film 13, the proportion of the inorganic coating film 13 itself per unit area of ​​the inorganic coating film 13 can be reduced by the large number of ultra-fine nanobubbles 14, and the amount of inorganic coating film 13 itself coated when the surface 12 of the article 11 to be coated is reduced, making it possible to reduce the amount of inorganic coating film 13 coated on the article 11. In addition, compared to a case in which the nanobubbles 14 (spherical spaces) are not dispersed and mixed in the inorganic coating film 13, the reduced amount of coating reduces the unit price of the coating film 13 per unit area of ​​the surface 12 of the article 11, and the surface 12 of the article 11 can be coated with the inorganic coating film 13 at low cost.

[0169] The inorganic coating film 13 made from the coating liquid 10 of Samples A to E has a reduced mass per unit area compared to when the spherical nanobubbles 14 (spherical spaces) are not dispersed and mixed therein, and therefore when the inorganic coating film 13 is applied to the surface 12 of the article 11 to be coated, it is possible to minimize the increase in weight of the article 11 including the inorganic coating film 13. For example, when the article 11 coated with the inorganic coating film 13 is an automobile, it is possible to minimize the increase in weight of the automobile including the inorganic coating film 13, and prevent a decrease in fuel economy and acceleration performance of the automobile.

[0170] The inorganic coating films 13 made from the coating liquids 10 of samples A to E have a nanobubble 14 content in the inorganic coating film 13 in a range of 10 to 95 vol.%, preferably in a range of 30 to 95 vol.%, and more preferably in a range of 50 to 95 vol.%, and the nanobubbles 14 are dispersed in the inorganic coating film 13 within 1 mm 2 The total number of nano bubbles per 14 is 10 7 ~10 12 pieces / 1mm 2Since the thickness of the inorganic coating film 13 is within the range of 5 nm to 1 μm, and preferably within the range of 50 nm to 500 nm, the inorganic coating film 13 does not have defects such as pinholes or slits, and can maintain corrosion resistance for a long period of time.

[0171] The inorganic coating film 13 made from the coating liquid 10 of Samples A to E has a film thickness of 1 μm or less, preferably 500 nm or less, so that even if the article 11 to be coated is deformed, the inorganic coating film 13 follows the deformation and can maintain the coating state of the surface 12 of the article 11 with the inorganic coating film 13 for a long period of time. Even if the inorganic coating film 13 contains nanobubbles 14, which are ultrafine bubbles, dispersed (dispersed and dissolved), the inorganic coating film 13 hardens with glass as the main component to form a glass coating layer that is approximately 100%. Therefore, the inorganic coating film 13 has excellent impact resistance and corrosion resistance, can maintain the coating state of the surface 12 of the article 11 for a long period of time, and can reliably protect the surface 12 of the article 11 with the inorganic coating film 13.

[0172] The inorganic coating films 13 made from the coating liquid 10 of Samples A to E exhibit excellent impact resistance and excellent corrosion resistance when the film thickness is in the range of 100 nm to 1 μm, as shown in the correlation in Fig. 7. When the film thickness of the inorganic coating film 13 is less than 50 nm, during a chemical reaction between the coating liquid 10 and the moisture on the surface 12 of the article 11, a volatilization path for the volatilized gas is generated in the film layer in a linear manner in the vertical direction of the surface 12, and pinholes may be generated in the inorganic coating film 13. However, when the film thickness of the inorganic coating film 13 is 50 nm to 500 nm, the volatilization path for the volatilized gas becomes a complex path, so that pinholes are not generated in the inorganic coating film 13 and corrosion resistance can be maintained.

[0173] Polysilazane and siloxane, which are components of the inorganic coating film 13 made from the coating liquid 10 of samples A to E, contain methyl groups (CH 3 ) content is formed to be 50% or more, so that hydrophobic methyl groups (CH 3 Since the inorganic coating film 13 has a structure in which many hydrophobic methyl groups (CH 3 ) and hydrophilic hydroxyl groups (OH) derived from the hydrolysis product of the alkyl silicate condensation product are mixed and coordinated, thereby improving the drainage property on the surface of the inorganic coating film 13 and providing a high antifouling effect.

[0174] The inorganic coating film 13 made from the coating liquid 10 of Samples A to E is formed on a smooth surface with nano-level minute unevenness 37 (dimples) formed on the surface, which makes it difficult for moisture or foreign matter to adhere to the surface of the inorganic coating film 13, and has high water repellency and high antifouling effect. In addition, since the condensation reaction of the organic polysilazane and / or siloxane occurs rapidly, the time required to form the inorganic coating film 13 from the coating liquid 10 can be shortened. [Explanation of symbols]

[0175] 10 Coating liquid 11 Goods 12 Surface 13 Inorganic coating film 14 Nanobubbles 15 Nanobubble mixing device 16 Coating liquid storage tank 17 Gas supply tank 18 Water Pump 19 Air supply pump 20 Static fluid mixer (nanobubble generator) 21 Coating liquid storage tank 22 Water supply pipeline 23 Air supply line 24 Mixing line 25 Supply pipeline 26 Cylinder Unit 28 Surface layer 29 Covering layer 30 back layer 31 Covering layer 32 Covering layer 33 Middle Class 34 Crosslinked structure 35 Uneven part 36 Anchor section

Claims

1. In an inorganic coating film, which is mainly composed of glass in a hardened state and covers the surface of an article to be coated, The inorganic coating film is characterized in that a large number of independent fine spherical spaces are dispersed and mixed inside the inorganic coating film.

2. The spherical space is formed by nanobubbles, and the average particle diameter D of the nanobubbles 90 is less than 1 μm, and the average particle size D 90 2. The inorganic coating film according to claim 1, wherein the nanobubbles are dispersed and mixed in the inorganic coating film at a predetermined concentration.

3. The average particle size D of the nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and the average particle size D 50 3. The inorganic coating film according to claim 2, wherein the nanobubbles are dispersed and mixed in the inorganic coating film at a predetermined concentration.

4. 4. The inorganic coating film according to claim 3, wherein the content of the nanobubbles in the inorganic coating film is in the range of 10 to 95 vol. %.

5. 5. The inorganic coating film according to claim 4, wherein the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of these.

6. A coating solution which, when hardened, forms an inorganic coating film mainly composed of glass on the surface of an article to be coated, The coating liquid is produced by mixing a liquid silicon material consisting of at least one of polysilazane and siloxane, an alkyl silicate condensate, and an inert organic solvent in a predetermined mixing ratio, and a large number of independent fine spherical spaces are dispersed and mixed inside the coating liquid.

7. The spherical space is formed by nanobubbles, and the average particle diameter D of the nanobubbles 90 is less than 1 μm, and the average particle size D 90 The coating liquid according to claim 6, wherein the nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration.

8. The nanobubbles are dispersed and mixed in the coating liquid in a negatively charged state, and the average particle diameter D of the nanobubbles 50 is in the range of 1 nm or more and less than 500 nm, and the average particle size D 50 The coating liquid according to claim 7, wherein the nanobubbles are dispersed and mixed in the coating liquid at a predetermined concentration.

9. 9. The coating liquid according to claim 8, wherein the content of the nanobubbles in the coating liquid is in the range of 10 to 95 vol. %.

10. 10. The coating liquid according to claim 9, wherein the blending ratio of the silicon material to the total mass of the coating liquid before the nanobubbles are mixed therein is in the range of 30 to 60 wt %, the blending ratio of the alkyl silicate condensate to the total mass of the coating liquid before the nanobubbles are mixed therein is in the range of 10 to 15 wt %, the blending ratio of the inert organic solvent to the total mass of the coating liquid before the nanobubbles are mixed therein is in the range of 30 to 60 wt %, the viscosity of the coating liquid at 20° C. into which the nanobubbles are dispersed and mixed is in the range of 0.98 to 1.008 mPa s, and the rising speed of the nanobubbles in the coating liquid at 20° C. into which the nanobubbles are dispersed and mixed is in the range of 0.000015 to 0.00005 mm / min.

11. 11. The coating liquid according to claim 10, wherein the gas that forms the nanobubbles is any one of air, nitrogen, argon, helium, xenon, neon, krypton, radon, hydrogen, oxygen, ozone, methane, ethylene, propane, butane, acetylene, ethanol, fluorine, chlorine, bromine, iodine, ammonia, hydrogen sulfide, sulfur dioxide, carbon monoxide, and carbon dioxide, or a mixed gas of two or more of them.

Citation Information

Patent Citations

  • Coating liquid and coating method

    JP2021014514A